XsiAMT1.1a was identified as a novel ammonium uptake functional gene and its overexpression combined with GA4 application significantly increased yield in Arabidopsis thaliana - Xiao Han; Zhao-Hua Gong; Jie Cao; Li-Na Ye; Yuan Cheng; Yu-Xuan Du; Ting-Ting Zhao; Hai-Long Wu; Chang Zhang (Plant Science, 2026)

Corrigendum to “A case study of Lepiota brunneoincarnata poisoning with endoscopic nasobiliary drainage in Shandong, China” [Toxicon 161C (2019) 12-16] - Jian Sun; Hong-Shun Zhang; Hai-Jiao Li; Yi-Zhe Zhang; Qian He; Jun-Jia Lu; Yu Yin; Cheng-Ye Sun (Toxicon, 2026)

Synergistic analysis and vertical transport attribution of carbon monoxide surface concentrations and satellite column loadings over China - Shuo Wang; Jason Blake Cohen; Kai Qin; Luoyao Guan; Pravash Tiwari; Ye Feng; Xiaolu Li; Qin He; Zhengqiang Li; Cheng Fan; Dacheng Wang (Remote Sensing of Environment, 2026)

PpPRE1 and PpPRE2 mediate gibberellin-induced internode elongation by regulating brassinosteroid biosynthesis in peach - Huanbing Lu; Mengmeng Zhang; Ning Liu; Bo Zhao; Jun Cheng; Bin Tan; Xianbo Zheng; Wei Wang; Xia Ye; Haipeng Zhang; Xiaobei Wang; Zhiqian Li; et al. (Plant Science, 2026)

Asymmetry of lava tube skylight segments: Segment structural analysis and implications for future lunar exploration - Haiting Yang; Zhizhong Kang; Teng Hu; Liang Gao; Yan Li; Cheng Peng; Chenming Ye; Haoxiang Hu; Qiao Yang (Icarus, 2026)

Structural and functional characterization of whey protein isolate-polyphenol covalent conjugates prepared via electrochemical oxidation, alkaline treatment, and free radical grafting - Jinshun Ye; Ying Xu; Yuting Li; Wenxue Cheng; Xiaozhen Liu; Xiangying Yu; Jingkun Yan; Lin Li (Food Research International, 2026)

Exploring the effect of micro-pressure stewing technology on the formation of key aroma compounds in pork by means of lipidomics and lipid-derived free radical analysis - Huan Liu; Shuqi Zhao; Guofeng Jin; Pi Li; Jianjun Li; Peng Gao; Jiangtao Xing; Jianmei Zhang; Ye Zhang; Weiting Wang; Pengfei Du; Chengyu Zeng; et al. (Food Research International, 2026)

Concentration-dependent interfacial reconstruction governs the thermal stability of whey protein microgels-sucrose ester hybrid Pickering emulsions - Xiang Li; Yingxiang Li; Qianyi Ye; Yaoxi Zhang; Sihan Cheng; Yikai Chen; Hong Liu; Tongfei Shi; Jie Xiao (Food Hydrocolloids, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

Dynamic moisture content and an integrated climatic-factor model for a porous facing brick after wind-driven rain in hot-humid regions - Zifeng Ye; Li Li; Xiaoqing Zhou; Mingtao Ma; Zhulin Xiong; Junfeng Cheng; Xinyang Li; Huaijie Peng (Energy and Buildings, 2026)

An approach based on geometric and spectral features for automatic identification of rock mass discontinuities from multi-view UAV photogrammetry - Duo Li; Lei Huang; Chunlei Wang; Cheng Zhang; Wu Ye; Libin Wu; Weili Zhang; Li Lv (Engineering Geology, 2026)

High-pressure CO₂ spraying of electret melt-blown polypropylene for piezoelectric self-sensing respiratory monitoring masks - Jiahui Xu; Xiaoyue Zou; Ning Cao; Yunchen Yao; Yuxin Jia; Na Zheng; Zhenshu Chen; Youqiang Yang; Zhanquan Lu; Xiangrong Chen; Pengfei Xie; Cheng Li; et al. (Chemical Engineering Journal, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

Soil macrofauna mucus bacterial community: Insights from cultured earthworms and snails - Jia-Jia Gu; Ming-Xin Li; Shuai-Fei Ye; Qiu-Yu Gan; Si-Si Chen; Cheng-Wei Tao; Jing Wen; Xin-Li An; Yu-Ling Jiang; Hong-Tao Wang (Soil Ecology Letters, 2026)

Environmental cadmium disrupts placental angiogenesis and fetal growth via enhancing m6A modification in Wwp2 - Cheng-Fang Sun; Ye-Xin Luo; Xin-Xin Zhang; Rui Pan; Yu-Xi Wu; Jia-Ying Chen; Xin-Run Wang; Lan-Lan Wu; Si-Ting Liu; Wei Chang; Zhi Yuan; Da-Min Zhu; et al. (Environmental Pollution, 2026)

Reinforcement learning enhanced zeroth-order optimization for large-scale multiobjective optimization problems - Yonglin He; Cheng He; Zhichao Lu; Ye Tian; Handing Wang; Yinglan Feng; Hongbin Li (Swarm and Evolutionary Computation, 2026)

Selective reduction of hazardous volatiles from baijiu using spent grain-derived activated carbon: Flavor preservation and DFT-elucidated adsorption mechanisms - Ziyang Wu; Yunran Shen; Yahan Yan; Yaqi Teng; Jie Lin; Huan Cheng; Hehe Li; Jinyuan Sun; Xingqian Ye; Mingquan Huang; Baoguo Sun (Food Chemistry, 2026)

Preparation and performance evaluation of a novel Tween 80-based microemulsion system for the remediation of petroleum hydrocarbon-contaminated soil using soil washing test - Peng Ye; Zhibin Liu; Chenfei He; Haitao Yu; Changsong Zhang; Xueke Zang; Hang Cui; Zhengbing Li; Liangliang Lu; Shiju Cheng (Environmental Research, 2026)

Coordination-driven self-assembly of cerium-baicalein nanozyme promotes spinal cord injury repairing by simultaneously scavenging mitochondrial ROS and reprogramming macrophage polarization - Zhefan Xie; Cheng Peng; Xiaofeng Li; Yuqi Zhao; Shenghang Liu; Xuenian Ye; Yuxue Wang; Wenchong Tan; Huimin Hu; Jianqiang Li; Yanming Ma; Chunlai Fu (Chemical Engineering Journal, 2026)

Multiscale modelling of crystalline swelling-driven triple-pore evolution in bentonite buffer for HLRW disposal - Wen-jie Dai; Yong-gui Chen; Yu-cheng Li; Zhao Sun; Wei-min Ye; Jing-li Xie; Sheng-fei Cao; Zhen-yu Yin (Applied Clay Science, 2026)

Schizantherin B alleviates cisplatin-induced ototoxicity and does not interfere cisplatin-based chemotherapy in a breast cancer model - Zirui Zhao; Lei Han; Zhijiao Xu; Benyu Nan; Honghai Tang; Dingding Dong; Zhen Zen; Ziwen Gao; Cheng Ye; Xinsheng Huang; Jianning Zhang; Geng-Lin Li; et al. (Archives of Toxicology, 2026)

Unveiling the molecular diversity of toxins and non-toxins in the medicinal sea snake Hydrophis cyanocinctus through integrated venomics investigation - Jiayi Lin; Zhaoran Yu; Yue Cheng; Sheng Han; Ruiwei Ye; Dandan Yang; Xiawen Dang; Haorui Dai; Zhiping Zhao; Yonghong Zhou; Yiming Lu; An Li (Toxicon, 2026)

Retraction notice to “Determining the spatial non-stationarity underlying social and natural environment in thyroid cancer in China” [Sci. Total Environ. 870 (2023) 162009] - Xiyu Zhang; Yongqiang Lai; Xiaodan Bai; Bing Wu; Wenjing Xiang; Chenxi Zhang; Guihong Geng; Wenqing Miao; Qi Xia; Qunhong Wu; Huiying Yang; Yanjie Wang; et al. (Science of The Total Environment, 2026)

Regulated external lithium supply enables high-energy sulfurized polyacrylonitrile-graphite fiber batteries - Tianrui Li; Chuanfa Li; Qian Ye; Yi Jiang; Longmei Ma; Jiaqi Wang; Yiqing Cheng; Kun Zhang; Jiahe Qu; Yingfan Chang; Shiqi Sun; Siwei Cao; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Multi-omics analysis of the gill–gut axis in Scylla paramamosain under acute low-salinity stress: Implications for ion and osmotic regulation - Yiming Li; Yucong Ye; Lang Lou; Zongli Yao; Yanwu Ma; Yonghui Feng; Wei Liu; Hui Wu; Zhen Sun; Zihe Cheng; Yunlong Zhao; Qifang Lai (Marine Environmental Research, 2026)

Synthesis and characterization of high-entropy Lu2Yb2Tm2Er2O12 rare-earth oxide nanoparticles for photocatalytic applications and their electronic structure studies by density functional theory - Ehsan Ghasali; Ye Cheng; Ehsan Moradpur-Tari; Hossein Maleki-Ghaleh; Jan Paczesny; Saleem Raza; Asif Hayat; Amirhosein Pakseresht; Li Jie; Yasin Orooji (Journal of Environmental Chemical Engineering, 2026)

A sensory-calibrated electronic nose method for odor intensity quantification and grade identification in refrigerators - Shiwen Cheng; Li’ang Yin; Xiao Ye; Xiaozheng Liu; Yumei Qin; Yaqing Song; Suyun Zhang; Tengfei Yu; Chonghui Zhang; Shiyi Tian (Food Research International, 2026)

Spatial metabolomic profiling of ripening pepper fruit (Capsicum annuum L.) by MALDI-MSI: Decoding metabolic heterogeneity and its role in quality attribute regulation - Yuanling Yang; Chaochao Liu; Zhuping Yao; Chenxu Liu; Meiying Ruan; Rongqing Wang; Hongjian Wan; Qingjing Ye; Zhimiao Li; Ming Diao; Yuan Cheng (Food Chemistry, 2026)

Core-shell biochar-zeolite fertilizer with starch coating: Boosting nutrient use in saline-alkaline rice soils via smart drone delivery & economic assessment - Chang Dong; Aosheng Bai; Xu Zhao; Yang Cheng; Qinglong Chen; Phoutthasone Sibounavong; Xin-Fu Ye; Yongfu Li; Yanjiang Cai; Jie Zhu; Ruohui Lu; Bing Yu (Environmental Research, 2026)

Conservation tillage enhances soil aggregate stability and maize yield in the wind-water erosion crisscross zone - Jun Ye; Juan Li; Yejia Di; Xiuqing Wei; Yuchen Cheng; Lei Tian; Yongfeng Ren; Zhenwei Li; Liyu Chen; Zhanyuan Lu (Ecological Engineering, 2026)

Click-crosslinked nano-hydrogel enables metabolic immune reprogramming for diabetic foot ulcers - Heng Gong; Tingjiang Gan; Xikun Ma; Ye Wu; Yaxing Li; Shijiu Yin; Biao Cao; Xiangtian Deng; Cheng Zheng; Yunbing Wang; Hui Zhang (Science China Life Sciences, 2026)

Innovative technologies and future perspectives in tumor microbiomics - Wan-Ting He; Xiaofang Xing; Fei Wang; Le Li; Ye Cheng; Gang Yao (Science China Life Sciences, 2026)

Egg Disease in Spodoptera litura (Fabricius) Caused by Aspergillus ochraceus and Its Metabolic Phenotype - Wen-Jie Lei; Yan Zhao; Qin-Ye Zhang; Hao-Jun Wang; Xiang-Li Dong; Jian-Yu Meng; Liu-Ti Cai; Hui-Zi Wu; Han-Cheng Wang (Current Microbiology, 2026)

TRIF signaling is essential for the activation of dendritic cells during porcine rotavirus infection - Yu Sun; Tianming Niu; Ran Zhang; Danni Li; Mingyang Cheng; Chenxi Jiang; Yiran Shao; Hongyuan Wang; Ziqun Guo; Wentao Yang; Xin Cao; Chunfeng Wang; et al. (Veterinary Microbiology, 2026)

The value-of-green in second-hand bulk carrier valuation: a hybrid machine learning approach - Kevin X. Li; Yongxuan Feng; Xiwen Bai; Kum Fai Yuen; Guanqiong Ye; Liangqi Cheng (Transportation Research Part D: Transport and Environment, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Increased microbiological risks caused by extreme precipitation in a drinking water system in mountainous area: From source to tap - Xinyan Xiao; Chen Cheng; Xiuxiu Wang; Ziqi Luo; Lihua Li; Siming Hu; Dongmei Zhu; Mingbao Feng; Chengsong Ye; Xin Yu (Journal of Hazardous Materials, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

The binding mechanism of an iron-chelating peptide from duck plasma and insights into its absorption-enhancing effect in Caco-2 cells - Jiulan Peng; Cancan Luo; Hanyu Guo; Zhiyu Li; Ying Zhou; Ye Zou; Biao Yang; Mei Cheng; Jingjing Ma; Weimin Xu; Daoying Wang; Jing Yang (Food Research International, 2026)

Mechanistic insights into glufosinate-ammonium (GLA)-Induced brain injury revealed by LC-MS/MS-based metabolomics - Huan-le Ye; Xin-xin Zheng; Mian-mian Li; Zhi-qiang Zhang; Liu-xu Chen; Wen-jing Zhang; Ren Cheng-Han Fan; Guo-xin He; An-cong Xu (Chemico-Biological Interactions, 2026)

Independent and joint effects of ambient temperature and relative humidity on fetal distress: effect modification by air pollutants - Hua Xiao; Yi Wang; Zongli Qi; Ziwei Ye; Liping Li; Li Mao; Peng Hu; Yuefei Li; Haoyun Zhang; Yao Cheng; Hao Wang; Ping Chen; et al. (International Journal of Biometeorology, 2026)

Inception-level signal amplification: Cascaded DNAzyme-Cas9 nickase achieves sub-nanomolar kanamycin tracking - Wen Xu; Yutian Cheng; Kexin Sun; Yue Wu; Yiming Xu; Jiang Ye; Pengfei Li; Haizhen Wu (Analytica Chimica Acta, 2026)

Targeting Pyruvate Kinase M2: Signal Transduction Pathways and Exploration of Cancer Therapeutic Strategies - Jiaxing Wang; Wenyu Zhang; Nana Shen; Pan Li; Wentao Xie; Shuya Wang; Ye Cheng; Lin Zhao; Yang Yang; Huadong Zhao (The AAPS Journal, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

PpZAT10 inhibits PpTST1 expression to regulate sugar accumulation in peach (Prunus persica) fruit - Qinqi Liu; Beibei Feng; Liuqing Han; Dongsheng Wang; Kexin Liu; Xiaobei Wang; Nan Hou; Lei Wang; Xianbo Zheng; Xiaodong Lian; Jun Cheng; Wei Wang; et al. (Plant Science, 2026)

MXene and polyethyleneimine co-modified chitosan aerogel efficiently removes multiple pigments from molasses wastewater: Competitive adsorption behavior and mechanism - Wanbing Cheng; Fengping Pang; Yongwei Zhu; Shaohui Wei; Lisha Ye; Jianbin Li; Ligao Deng (Journal of Environmental Chemical Engineering, 2026)

Contribution of various pectin fractions and internal condition to gel formation in wooly peach fruit during cold storage - Xiangwen Fang; Jianfen Ye; Cheng Li; Xi Yang; Jing Li; Yingying Wei; Shu Jiang; Yi Chen; Feng Xu; Xingfeng Shao (Food Chemistry, 2026)

Over-agglomeration and eco-efficiency trade-offs in China's textile industry: An environmental pressure - based assessment - Siyuan Zhang; Rentao Zhang; Ye Liang; Cheng Xie; Chenye Xu; Chensi Shen; Fang Li (Environmental Impact Assessment Review, 2026)

PpBRC1 negatively regulates branching via modulating GA signal transduction gene PpGID1b in peach (Prunus persica) - Yulu Wu; Yajia Zhang; Junjie Zhang; Xiaobei Wang; Haipeng Zhang; Xiaodong Lian; Nan Hou; Xianbo Zheng; Jun Cheng; Wei Wang; Langlang Zhang; Xia Ye; et al. (Plant Cell Reports, 2026)

Taxonomy and Phylogeny of the Little-Known Ciliate Genus Cyclotrichium: With Special Reference to Two New Species - Zijun Cheng; Bowen Ye; Gang Li; Xiping Lian; Yehui Tan; Xiaofeng Lin; Weiwei Liu (Journal of Ocean University of China, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Inner-radius-controlled tuning of surface-wave bandgaps in hexagonal locally resonant periodic pile barriers: experiments and complex band-structure modelling - Jinglei Liu; Jinyuan Cao; Jing Guo; Xiuxin Li; Xinglei Cheng; Tengfei Wang; Shuzheng Shi; Qingzhi Ye (Soil Dynamics and Earthquake Engineering, 2026)

Distribution characteristics, source apportionment and risk assessment of heavy metal pollution in typical redevelopment sites in Jinshan District, Shanghai, China - Cheng Shen; Chenyan Sha; Tianhao He; Zhongchun Yan; Xiurong Chen; Kuangfei Lin; Haichao Chen; Jian Wu; Ye Li; Min Liu (Journal of Environmental Sciences, 2026)

Solid waste dumping differentially impacts soil prokaryotic, fungal, and viral communities: Insights from metagenomics - Rongzhou Jin; Can Chen; Jingru Zhang; Yanying Li; Ye Wu; Feifan Wang; Zhipeng Chen; Ting Huang; Qijie Cheng; Xinlin Yu; Pu Jia (Journal of Environmental Sciences, 2026)

Simultaneous removal of fluoride and disinfection by-product precursors through Zr salt enhanced coagulation - Zhanghan Li; Pin Wang; Cheng Ye; Jiacheng Luo; Yayun Zhang; Wenhai Chu (Journal of Environmental Sciences, 2026)

Highland red rice-derived resistant starch and pigment extracts exert combined anti-hyperglycemic effects via the gut microbiota-PYY/GLP-1 pathway - Leyi Zhao; Xinyu Shao; Liyuan Wang; Ziqing Cheng; Yawen Zeng; Shiquan Si; Xuhua Yang; Xia Li; Xiaomeng Yang; Lina Ye; Yuji Peng; Michael Zhang; et al. (Food Bioscience, 2026)

Perfusion process-oriented metabolic engineering enhances 1,3-dihydroxyacetone production efficiency in Gluconobacter thailandicus - Yang Sun; Zilong Hu; Yuwei Shan; Rui Wang; Tang Liu; Kuiqi Jin; Qingxuan Miao; Cheng Ye; Jianqi Nie; Daiyin Zuo; Yinbiao Xu; Hua Li; et al. (Chemical Engineering Journal, 2026)

Trio-active bone scaffold with multivalent ion doping establishes an osteo–angio–immune bone regenerative axis - Jiren Yan; Xiang Li; Teng Ye; Weinan Cheng; Yaping Li; Gen Wen; Fei Zhang; Linyang Chu (Chemical Engineering Journal, 2026)

Short-term exposure to traffic-related air pollution and cause-specific mortality among people living with HIV/AIDS (PLHIV) in Anhui, China: A case-crossover study - Yongsheng Ye; Yangguang Wang; Jinling Song; Liping Gong; Zeyang Li; Meng Gao; Seying Dai; Jian Cheng; Yinguang Fan (International Journal of Biometeorology, 2026)

Human MAITregs possess diverse TCR repertoires and are functionally supported by glycolysis - Maoyu Tang; Xinying Li; Xudong Yang; Changfeng Zhao; Yuwei Zhang; Sanwei Chen; Zhenghui Ye; Liujin Hou; Yusheng Chen; Rong Lv; Hongchuan Zhao; Xiaowen Cheng; et al. (Science China Life Sciences, 2026)

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

Quantifying the uncertainty contribution in runoff projection and the time scale effects - Zhanling Li; Yingtao Ye; Cheng Xie; Xiaoyan Zhai (Journal of Hydrology, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Synergistic utilization of circulating fluidized bed fly ash and pulverized fly ash in low-carbon solid waste cementitious materials: Performance and hydration mechanism - Jianmin Li; Liwen Guo; Ye Li; Jiayong Zhang; Cheng Zhang; Hui Pan; Xiao Cui; Xiaofan Zhao (Journal of Environmental Chemical Engineering, 2026)

Microemulsion flushing of petroleum hydrocarbons in porous media: Microfluidic insights into residual oil morphologies and removal mechanisms - Peng Ye; Zhibin Liu; Chenfei He; Haitao Yu; Changsong Zhang; Xueke Zang; Hang Cui; Zhengbing Li; Liangliang Lu; Shiju Cheng; Quanbin Jin (Journal of Environmental Management, 2026)

Automated multi-chemical dosing control based on machine learning for magnetic coagulation in aquaculture wastewater - Chaoyi Guo; Miao Lv; Yang Yang; Tianming Chen; Xiaolong Bai; Cheng Ding; Wenlu Li; Fan Chen; Wanxin Yin; Ye Yuan (Journal of Environmental Management, 2026)

Bacillus velezensis-derived methylmalonic acid inhibits Aspergillus flavus growth and aflatoxin biosynthesis by interfering with tryptophan metabolism - Ming Li; Qin Han; Xiulan Zhao; Yuxuan Hong; Ye Zhu; Can Liu; Jinyan Chai; Ling Cheng; Xiaofeng Yue; Xiaoqian Tang; Jing Mao; Qi Zhang; et al. (Chemical Engineering Journal, 2026)

Stage-specific ion release from dual-crosslinked alginate/boron-doped bioactive glass hydrogel accelerates infected wound healing - Fuqiang Song; Linyuan Jiang; Anqi Ye; Rong Huang; Anwen Lai; Longyang Xu; Wei Shen; Junjun Li; Jiayan Hui; Andi Suo; Yanzhi Xiong; Xiaoyu Dong; et al. (Carbohydrate Polymers, 2026)

Quantifying and Predicting Heterogeneity in Marine Clastic Reservoirs Through Machine Learning: Methodology and Applications - Yu Ye; Chao Cheng; Jie Chen; Xiangjun Liu; Xi Li; Guo Chen; Liang Cheng; Jie Fang; Peiyan Li (Natural Resources Research, 2026)

A new method for solving the magnetotelluric forward problem in geophysics - Shuai Zhang; Mei Huang; Yanting Cheng; Fawang Ye; Yaodi Li; Yiyuan Du; Shiju Jin; Yuanyuan Zhao; Fenglei Niu (Annals of Nuclear Energy, 2026)

Decoding the molecular network communication mechanism of ketamine’s antidepressant effects - Ye Li; Qilong Cheng; Guoxin Lin; Kaiming Duan; Saiying Wang (Psychopharmacology, 2026)

A review of transcriptional control and adaptive functions in terpenoid biosynthesis: Focus on MYB regulatory networks - Sihui Guan; Zhuping Yao; Chenxu Liu; Rongqing Wang; Meiying Ruan; Hongjian Wan; Qingjing Ye; Zhimiao Li; Ming Diao; Yuan Cheng (Plant Science, 2026)

Allelopathic metabolite accumulation and microbial dysbiosis underlying continuous cropping disorder in the Panax ginseng rhizosphere - Yang-Bin Lai; Jia-Qi Wang; Li-Ye Cheng; Yuan Zhao; Jin-Qi Wang; Jin-Hea Jeoun; Qi Yan; Chang-Bao Chen; En-Peng Wang (Physiological and Molecular Plant Pathology, 2026)

Genomic insights into stepwise selection reshaping fruit traits and male-biased selection driving hermaphroditism in papayas - Changmian Ji; Ruizong Jia; Yuliang Zhang; Xiaoxi Du; Xueying Huang; Huiliang Li; He Dai; Yu Wang; Qian Jiang; Zhengnan Xie; Shanshan Huo; Yang Cao; et al. (Molecular Plant, 2026)

A machine learning framework bridging heavy metal contamination and human health risks in agricultural soils of the Yangtze River Delta (2001–2030) - Luming Xiao; Pu Feng; Yuehong Liang; Bing Xia; Yang Ye; Huijun Liu; Wenlu Zhao; Zhiheng Li; Kaiming Cheng; Jie Chen (Journal of Hazardous Materials, 2026)

Isotopic tracing of lead for source-specific probabilistic health risk assessment of heavy metals in soils of Lanzhou, China - Yang Lan; Yan Li; Ke Liu; Long Chen; Haoran Huang; Xinyu Cheng; Zi Ye; Yujie Jiang; Meixian Wang (Journal of Geochemical Exploration, 2026)

Effects of tillage practices on aggregate-associated soil organic carbon fractions and maize yield - Xiuqing Wei; Jun Ye; Juan Li; Yejia Di; Yuchen Cheng; Lei Tian; Kun Zhao; Shuli Wei; Liyu Chen; Zhenwei Li; Zhanyuan Lu (Journal of Environmental Management, 2026)

Temperature-driven metabolic reprogramming in starter cultures impairs rheological properties and flavor release in fermented milk: A multi-omics approach - Shasha Cheng; Ye Wang; Baolei Li; Baochao Hou; Weilian Hung; Jian He; Chao Liang; Yujun Jiang; Yu Zhang (Food Chemistry, 2026)

Optoelectronic synaptic transistor array based on CsPbBr3/grating-patterned IDTBT heterojunctions for neuromorphic visual fatigue sensing - Jiajie Hong; Zhiqian Wei; Zunxian Yang; Yue Chen; Luxi Yuan; Shangwei Ye; Xudong Jiang; Yuting Bai; Benfang Liu; Zhiyu Yuan; Wenxin Zhang; Jie Li; et al. (Chemical Engineering Journal, 2026)

High-performance ethanol gas sensor based on stepped and hollow ZnSnO3/Co3O4 heterostructures - Ye Tian; Jie Wang; Junhao Wang; Jikai Luo; Zhengwu Zou; Dongsheng Li; Cheng Suo; Yuejun Li; Xiaoyan Jin; Mao Peng; Xing Chen (Chemical Engineering Journal, 2026)

Environmental filtering of microbial specialists drives divergent C, N, and S cycling in grasslands: Vegetation buffering maintains microbial diversity amidst soil moisture contrasts - Yiming Dai; Haining Wang; Qixiu Cheng; Yiming Zhang; Ye Cui; Huan Ma; Xiaoyu Li; Daolong Xu; Jin Chen (CATENA, 2026)

Effects of Seepage Pressure and Erosion Solution on the Permeability Characteristics of a Single Granite–Concrete Fracture - Lei Gan; Zhuo Yang; Zongliang Zhang; Lei Xiong; Jun Liu; Jie Ren; Shi Cheng; Lechen Li; Wenbin Ye; Zhi Liu; Yu Liu (Rock Mechanics and Rock Engineering, 2026)

Andrographolide blocked the progression of endometriosis by promoting ferroptosis via inhibiting anabolism of serine - Wei Ye; Nie Zhang; Jiaoyu Li; Fei Wang; Xiaoying Liu; Ruixin Zhang; Hongxu Chen; Linghui Cheng; Zhaolian Wei; Fengyu Zhu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The Fully Interactive Martian Dust Cycle Simulations by the GoMars Model - Shuai Liu; Li Dong; Xiangyu Xi; Xuan Cheng; Juanjuan Liu; Ye Pu; Yiyuan Li; Hongbo Liu; Mingyu Liu; Wei Xue; Junji Cao; Bin Wang (Advances in Atmospheric Sciences, 2026)

Global lysine crotonylation profiling reveals metabolic and stress-responsive mechanisms in Reynoutria japonica - Lei You; Peng Zhang; Hongbin Cheng; Yujie Deng; Haitang Xiong; Jumei Zhang; Zhengxiu Ye; Zezhi Zhang; Chen Li; Victor Manuel Martinez Espinosa; Chao Zhou; Lanlan Zheng; et al. (Journal of Plant Physiology, 2026)

Differential regulation of root iron plaque formation in a mangrove species, Kandelia obovata by biodegradable and conventional nanoplastics: Evidence from interfacial interactions, microbial communities, and redox conditions - Ming Li; Jie Gao; Nora Fung-Yee Tam; Haichao Zhou; Min Pan; Fred Wang-Fat Lee; Steven Jing-Liang Xu; Jian Liu; Kaixuan Deng; Peng Zheng; Cheng Ye; Xinran Ke; et al. (Environmental Pollution, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Characterization and biocontrol potential of two novel lytic phages vB_EtaS_2 and vB_EtaS_6 against Edwardsiella tarda in aquaculture - Yukun Wu; Shuai Ye; Senwu Liu; Jiahao Yu; Haibo Gao; Wei Feng; Xuchuang Cheng; Xiaoyu Zhao; Jianguo Zhao; Jifeng Zeng; Xin Zhang; Xueqian Wang; et al. (Aquaculture, 2026)

Urban development elevates methane and carbon dioxide emission in headwater streams - Suqin Zhao; Shenghui Cheng; Yang Ruan; Y.Jun Xu; Huaiwei Sun; Chen Ye; Wenzhi Liu; Siyue Li (Water Research, 2026)

The biomarker signatures in the Niujiaotang sulfide ore field: Exploring the role of organic matter in ore formation - Yong Cheng; Jia-Xi Zhou; Yuzhao Hu; Saihua Xu; Shengbao Shi; Yiming Wen; Qi Nie; Ye Zhou; Kai Luo; Xiaolin Tan; Liang Zhou; Yadong Li; et al. (Marine and Petroleum Geology, 2026)

Expanded species diversity of fungi in metalliferous mine tailings ponds and their potential ecological roles revealed by PacBio sequencing - Yanying Li; Ting Huang; Weihang Zeng; Rongzhou Jin; Ye Wu; Zhipeng Chen; Qijie Cheng; Xinlin Yu; Xiao-lin Luo; Guan-xiong Wu; Jia-wei Li; Pu Jia; et al. (Journal of Hazardous Materials, 2026)

A carbon sink calculation model for concrete buildings considering time-variant environment - Jia-cheng Xu; Bei Li; Ye Tian; Ruo-yi Zhao; Guo-yi Zhang; Qiang Zeng; Cong-cong Ma; Bo-Tao Huang; Hong-jing Xue; Yun-jian Li; Qing Cai (Environmental Impact Assessment Review, 2026)

Nonmetallic phosphorus doped Co3O4: Electronic structure modulation and high-performance acetone detection - Zhaohui Lei; Yinglin Wang; Yiyang Xu; Chen Wang; Songlin Li; Pengfei Cheng; Ye Tian; Shanghai Wei; Wei Gao; Luping Xu (Chemical Engineering Journal, 2026)

Biomass reforming to H2 and formic acid via an off-field electrocatalysis - Xiaolei Qu; Qing-Nan Wang; Ben Chang; Chuchu Cheng; Shengqi Chen; Shihua Ye; Jun Chen; Can Li (Chemical Engineering Journal, 2026)

Enhanced efficacy of anaerobic membrane bioreactor (AnMBR) for treating pharmaceutical wastewater with abundant protein particles - Ye Tian; Hui Cheng; Yupeng He; Haodi Feng; Wen Shi; Jie Sun; Yuyou Li; Yu Zhang; Min Yang; Zhe Tian (Chemical Engineering Journal, 2026)

3D printing of carbon-based scaffolds with aligned structures for anisotropic and high-performance electromagnetic interference shielding - Yuheng Jiang; Yun Gou; Ye Xu; Ningfeng You; Yanqin Huang; Shaohong Shi; Jiahui Xue; Zhunan Huang; Xiaodong Li; Xiumei Li; Lukas Sporrer; Quanquan Guo; et al. (Chemical Engineering Journal, 2026)

Green and efficient alkaline DES pretreatment for full-component fractionation of reed biomass: Hemicelluloses, uncondensed lignin and easily digestible cellulose - Haozhi Zhang; Qian Sun; Yi-Bing Liu; Cheng-Ye Ma; Jia-Long Wen; Zhenglong Li; Tong-Qi Yuan (Chemical Engineering Journal, 2026)

Effect of tillage practices on soil erodibility in wind-water erosion crisscross region - Jun Ye; Juan Li; Yejia Di; Xiuqing Wei; Yongfeng Ren; Yuchen Cheng; Lei Tian; Zhenwei Li; Liyu Chen; Zhanyuan Lu (CATENA, 2026)

Comprehensive virome analysis of soybean agroecosystems in China reveals geographic patterns and interfacial virus spillovers - Mengjia Xu; Ruixiang Cheng; Rong Yan; Hao Ai; Sijing Qiao; Pengbo Li; Jin Zhang; Tianyu Hu; Xiaoli Chang; Huawei Yang; Wenwu Ye; Ming Ding; et al. (Science China Life Sciences, 2026)

Anti-epileptic effect of saikosaponin a by inhibiting ferroptosis via the IL-17/Akt/ERK signaling pathway in the temporal lobe epilepsy model - Ping-Ping Li; Wen-Wen Wang; Jing-Tao Wang; Zi-Ao Xu; Xue-Fei Ji; Liao Guan; Lei Ye; Hong-Wei Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Brain Tissue-Derived Exosomal Proteomics Identifies Chemotaxis-Associated Protein Changes After Traumatic Brain Injury: An Exploratory Hippocampal Transcriptomic Comparison - Wei-can Chen; Xin-li Chen; Cheng-ye Lin; Yang-zi Huang; He-fan He; Yi-lin Zhou; Yi-bin Liu (Molecular Neurobiology, 2026)

Novel interface-enhanced bimetallic nanozyme-mediated magnetic integrated nanoplatform for integrated prevention and control of pathogenic bacteria - Xiaoyu Yu; Xin Zhang; Yuwei Ren; Rui Jiao; Hui Li; Mengyu Li; Weichao Wu; Na Ling; Danfeng Zhang; Jianghua Cheng; Yingwang Ye (Analytica Chimica Acta, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Combined toxicity of microplastics and heavy metals to terrestrial plants: A global meta-analysis integrating machine learning predictions - Ye-Qian Zhen; Tian-Hao Che; Yu-Xuan Song; Ya-Ming Wan; Hai-Han Jiang; Zuo-Zhou Yu; Miao Yu; Shi-Qi Xu; Cheng-Yong Li; Jing-Ya Zhou (Journal of Environmental Chemical Engineering, 2025)

Modulation of gut microbiota and storage stability of yogurt fortified with novel EPS-producing Lactiplantibacillus plantarum DPA1C - Xingjie Wang; Jinghui Lai; Cheng Ye; Liwen Tao; Yuchen Liu; Kaidi Hu; Jianlong Li; Qin Li; Ning Zhao; Shuliang Liu (Food Research International, 2025)

Integrating peroxidase-mimicking MOF-based composite nanozymes with molecular imprinting for dual-mode thiamphenicol sensing in animal-derived foods - Shujuan Chen; Xi Cheng; Wenjing Wang; Minglin Ye; Yuan Cai; Fujia Zhong; Likou Zou; Jianlong Li; Shuliang Liu; Kaidi Hu; Aiping Liu (Food Chemistry, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Progressive collapse resistance of one-way wet-connected precast concrete beam-slab-column substructures: Experimental and numerical investigations - Guisheng Chen; Xiaowei Cheng; Mengzhu Diao; Yi Li; Ye Lu (Engineering Structures, 2025)

HFPO-TA induces liver damage and ferroptosis in zebrafish by disrupting iron metabolism homeostasis - Lin Cheng; Zhonghua Fan; Yu Zhang; Xu Fang; Yuanyuan Wu; Hongru Liu; Lanxi Ye; Li Wang; Hui Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Dissolving microneedles loaded with Acanthopanax Senticosus-derived vesicles and PEI for antibacterial activity, cfDNA scavenging, anti-inflammation, and angiogenesis in diabetic wounds - Huiling Ye; Junze Tang; Wanting Liang; Yushan Li; Zhaoyi Ye; Jiasen Lin; Guining Cao; Yaoxun Zeng; Yu Sun; Meijing Wang; Ziqiao Li; Xin Cheng; et al. (Chemical Engineering Journal, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Cascade pH-responsive multi-drug delivery nanosystem actuates PANoptosis of triple-negative breast cancer - Zhechen Fan; Junqiu Ye; Sijia Yao; Zhongsheng Ji; Weisong Li; Jianping Zhou; Hao Cheng; Yang Ding (Chemical Engineering Journal, 2025)

Prebiotic effects and functional insights into gut microbiota mediated by Qingke β-glucan of different molecular weights in vitro fermentation - Lan Zhao; Xinran Yang; Peijie Ye; Zhihai Lan; Jiale Cheng; Li Li; Jia Wu; Wei Xu; Huibin Chen (Bioactive Carbohydrates and Dietary Fibre, 2025)

The 1357 bp deletion in β-thalassemia: molecular profiling and hematological characterization in a Guangxi cohort - Youqiong Li; Tianjie Zhou; Lihua Ye; Liang Liang; Shufu Cheng; Lihong Zheng; Xi He; Peixing Wan; Tongfeng Huang (Molecular Biology Reports, 2025)

20-Hydroxyecdysone Affects Hepatopancreatic Vitellogenin Synthesis in Chinese Mitten Crabs (Eriocheir sinensis) Through the PLC-PKC Pathway - Runqiang Cheng; Changsheng Gen; Ye Li (Journal of Ocean University of China, 2025)

Preparation of Nitrogen-Doped Fluorescent Carbon Quantum Dots and Detection Study of Tetracycline - Li Han; Hui Wang; Jiajia Ye; Fengcui Shi; Wen He; Xing Gao; Yan Gao; Chaoyue Shan; Haidi Cheng (Journal of Fluorescence, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

Asthenospheric upwelling-induced seismic activity in the eastern North China Craton: Evidence from viscosity obtained from an MT study - Baochun Li; Gaofeng Ye; Sheng Jin; Wenbo Wei; Letian Zhang; Hao Dong; Chengliang Xie; Yaotian Yin; Shaohuai Sun; Zhaoyuan Kang; Peng Ding; Yiwu Zhang; et al. (Tectonophysics, 2025)

Promoting acetate production on the in situ reconstructed Cu nanoislands via pressure-regulated CO adsorption and electroreduction - Rongxing Qiu; Jiaran Li; Jiafeng Du; Siwang Zhang; Lingzhi Ding; Jinlong Wan; Cheng Li; Jinyu Ye; Jin-Chao Dong; Yuanjie Pang; Jian-Feng Li; Shuliang Yang; et al. (Science Bulletin, 2025)

Reply to “Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China” - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Characterization and formation process analysis of peach fruit woolliness under low-temperature storage - Jiajia Xu; Jianfen Ye; Cheng Li; Yuqing Guo; Weixiang Jiang; Xi Yang; Yingying Wei; Shu Jiang; Yi Chen; Xingfeng Shao (Food Chemistry, 2025)

Hypervirulent/persistent genotype L. monocytogenes ST87/CC87 contamination in commercial fresh Flammulina velutipes production facility in China - Ruizhen Feng; Man Li; Qifan Sun; Jiayi Cai; Jianheng Cheng; Ying Zhang; Zhiwei Ye; Qingping Wu; Moutong Chen (Food Control, 2025)

Design of EVOH nanofibers aerogel integrated with phase change materials for sustained solar-driven seawater desalination - Ye Zhang; Yi Wu; Shanshan Li; Mengqi Wang; Ke Liu; Ming Xia; Qin Cheng; Jia Xu; Shanshan He; Dong Wang (Chemical Engineering Journal, 2025)

The spatial diversity of secondary organic carbon aerosols at the city level: insights from explainable machine learning - Xiaojian Xu; Cheng Wu; Chenglei Pei; Mei Li; Chunlei Cheng; Menghua Lu; Zhijiong Huang; Baoling Liang; Xinkun Fang; Mengxi Ye; Dui Wu (Atmospheric Environment, 2025)

Satellite remote sensing capturing intense ozone production over marginal seas in East Asia: evident influence on air quality in coastal cities - Jin Ye; Qihou Hu; Qin Gao; Ran Zhao; Wenjing Su; Chengxin Zhang; Xiaohan Wang; Ziwei Li; Cheng Liu (Atmospheric Environment, 2025)

Intercropping sunflower with amaranth to remediate cadmium-contaminated agricultural land: performance and mechanism - Zhuo-hui Wu; Feifan Wang; Mai Ye; Jingru Zhang; Zhiyi Li; Yunrong Xi; Rongzhou Jin; Yanying Li; Zhipeng Chen; Ye Wu; Ting Huang; Qijie Cheng; et al. (Plant and Soil, 2025)

Tubeimoside I inhibits the growth of triple-negative breast cancer via the NR3 C2/PI3 K/AKT signaling pathway - Qinxiang Zhang; Wenjin Cheng; Ye Li; Yubao Zhang; Yang Yu; Shijie Wei; Ying Yang; Wenfeng Zhang; Cun Liu; Qibiao Wu; Changgang Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Chlorchinaldol: A promising antiviral agent against iridoviruses in fish - Jia-Cheng Qin; Xiao-Ping Tan; Ying-Jie Jin; Guang-Shuo Wang; Shen-Ye Qu; Peng-Fei Li; Gao-Xue Wang; Fei Ling (Aquaculture, 2025)

Modeling of carbon sink for concrete structures: From hydration kinetics to climate-driven carbonation - Ye Tian; Jia-Cheng Xu; Guo-Yi Zhang; Zu-Shi Tian; Bei Li; Ruo-Yi Zhao; Qiang Zeng; Bo-Tao Huang; Dong-Ming Yan (Sustainable Chemistry and Pharmacy, 2025)

Antibiotic-induced perturbations in C–N metabolic networks, and associated gene pathways in soybean (Glycine max) seedlings - Jie Feng; Zhiheng Li; Qianqian Liu; Yuye Hu; Zikang Ye; Jinyi He; Zhiguo Fang; Lidan Wu; Kaiming Cheng; Huijun Liu (Journal of Hazardous Materials, 2025)

Corrigendum to “Visualizing the spatial distribution of metabolites in tomato fruit at different maturity stages by matrix-assisted laser desorption/ionization mass spectrometry imaging” [Food Res. Int. 206 (2025) 115973] - Sihui Guan; Chaochao Liu; Zhuping Yao; Chenxu Liu; Meiying Ruan; Rongqing Wang; Qingjing Ye; Hongjian Wan; Zhimiao Li; Guozhi Zhou; Ming Diao; Yuan Cheng (Food Research International, 2025)

Harnessing basic helix-loop-helix-mediated transcriptional reprogramming in mixotrophic Chlorella for synergistic carbon waste remediation and biofuel production - Yu-Feng Yang; Jin-Hua Mou; Yu-Cheng Yang; Lan-Lan Hu; Wen-Li Huang; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2025)

Organic nitrates in coastal aerosols: Seasonal dynamics, influencing factors, and formation pathways - Mengke Tian; Zhijian Ding; Jia Chen; Juntao Huo; Guochen Wang; Jian Xu; Hao Li; Ziwei Liu; Yunkai Wang; Nan Ye; Xiaofei Qin; Yanfen Lin; et al. (Atmospheric Environment, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Comparative Transcriptomic Analysis Reveals Key Growth-Related Genes and Alternative Splicing Events in Siniperca scherzeri - Hao Xu; Jian Jin; Yang Li; Yannian Wu; Zhiqiang Cheng; Maoyuan Wang; Xiaojun Ye; Mingyong Lai; Dongling Zhang (Marine Biotechnology, 2025)

Analysis of the shallow water bathymetric accuracy of ICESat-2 in combination with marine environmental factors - Sensen Chu; Ruihan Xu; Xuedong Zhang; Jian Cheng; Jizhe Li; Qixin Hu; Li Ye; Ziyang Qu (Marine Geodesy, 2025)

Hyperspectral Satellite-Derived Bathymetry Considering Substrate Characteristics - Li Ye; Sensen Chu; Hui Chen; Jian Cheng; Ruihan Xu; Ziyang Qu (Marine Geodesy, 2025)

Deciphering the venom components of Sea snakes: Integrating dual proteomic techniques to uncover the bioactive potential of Hydrophis curtus - Yingying Li; Haorui Dai; Zhiping Zhao; Ruiwei Ye; Sheng Han; Dandan Yang; Hanyu Pan; Jiayi Lin; Xiawen Dang; Yue Cheng; Zhaoran Yu; An Li; et al. (Toxicon, 2025)

Prevalence and related factors of antenatal depression in 11 provinces and cities of China: a 100,000 population-based study - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Arbuscular mycorrhizal fungi mediate rare taxa and network complexity in rhizospheric and endophytic bacterial communities of Allium schoenoprasum L - Yiming Zhang; Ye Cui; Qixiu Cheng; Zishan Li; Yiming Dai; Keqing Lin; Xiaoyu Li; Jin Chen (Rhizosphere, 2025)

Different Arbuscular mycorrhizal fungi species alter rhizospheric and endophytic bacterial diversity, network stability and function of Allium schoenoprasum L - Jin Chen; Qixiu Cheng; Yiming Zhang; Ye Cui; Yiming Dai; Keqing Lin; Zishan Li; Boyan Wang; Xiaoyu Li (Physiological and Molecular Plant Pathology, 2025)

Corrigendum to “Enhancing Sulfate Reduction in Microbial Electrolysis Cells: The Impact of Intermittent Electric Field and Extreme Conditions on Reaction Mechanisms and Functional Genes” [Journal of Water Process Engineering, volume 71, March (2025) 107199] - Zhibin Xia; Liang Qiao; Fei Chen; Xu Jiang; Pingting Li; Xing Zong; Yihan Wang; Feihong Wang; Luyan Zhang; Xiaolong Bai; Ye Yuan; Tianming Chen; et al. (Journal of Water Process Engineering, 2025)

Causal links between long-term exposure to the chemical constituents of PM2.5 and lung cancer mortality in southern China - Shimin Chen; Peiwen Ye; Jing Wei; Huanhuan Cheng; Yuqin Zhang; Yujiao Ma; Shirui Chen; Wenjing Wu; Tong Guo; Zhiqiang Li; Jie Jiang; Yujie Ma; et al. (Journal of Hazardous Materials, 2025)

Estrogenic and transgenerational effects of perfluorocarboxylic acids through estrogen-related receptor γ pathway - Sha Shi; Wei Zheng; Xi-Long Zhang; Minjie Li; Cheng Ye; Lu Chen; Wen-Jun Hong; Chuan-Hai Li; Huiyu Chi; Fangfang Li; Liang-Hong Guo (Journal of Hazardous Materials, 2025)

Pre-carbonization facilitates closed pore formation in asphalt-derived hard carbon for high-plateau-capacity sodium storage - Chong Xu; Dongyuan Zhang; Guang Ma; Shuang Liu; Gong Cheng; Junjie Fu; Ye Wang; Runyi Xu; Chen Ling; Sai Che; Yongpeng Cui; Yongfeng Li (Chemical Engineering Journal, 2025)

Hyper-tolerant chloride/phosphate-rich interphase embracing aggressive zinc electrochemistry in hydrated eutectic electrolytes - Guigui Liu; Zhiheng Shi; Yongchao Tang; Yue Wei; Jintu Qi; Jianping Yan; Zhenfeng Feng; Wencheng Du; Qi Yang; Minghui Ye; Yufei Zhang; Zhipeng Wen; et al. (Chemical Engineering Journal, 2025)

Identifying Immune Response Protein Biomarkers in Parkinson’s-Related Cognitive Impairment and Depression - Qiaozhen Su; Ting Lu; Yan Xu; Zhe Li; Hongfeng Liang; Chunye Zheng; Kunhong Li; Linshuang Ye; Zhixuan Ren; Dafeng Hu; Yan Huang; Lihua Zhu; et al. (Molecular Neurobiology, 2025)

Correction: Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)

Establishment and characterization of a new Chinese extrahepatic cholangiocarcinoma cell line, EBC-X1 - Yuanhui Su; Huan Tang; Xin Miao; Cheng Yu; Changpeng Chai; Wei Huang; Lu Li; Jieyu Zheng; Tao Xu; Fa Jin; Zhipeng Ye; Zhao Hu; et al. (Human Cell, 2025)

Impacts of environmentally persistent free radicals on the denitrification toxicity of photoaged tire wear particles in estuarine sediments - Jinyu Ye; Yuhan Zhang; Yuan Gao; Chen Li; Baoping Zou; Ruotong Cheng; Baoyan Chi; Xiangdong Xue; Carlos Domingo-Félez (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Modelling the crystalline swelling process of montmorillonite incorporating boundary effects - Wen-jie Dai; Yong-gui Chen; Yu-cheng Li; Wei-min Ye; Qiong Wang (Computers and Geotechnics, 2025)

Chemical constituents from Dictamnus dasycarpus Turcz. and their chemotaxonomy value - Yan Liu; Guangzhi Li; Ye Sun; Jiatong Wu; Shiqi Xu; Juan Pan; Junnan Li; Luxin Li; Zhichao Hao; Wei Guan; Yuanyuan Zhou; Qi Shi; et al. (Biochemical Systematics and Ecology, 2025)

Characterization and Risk Assessment of Heavy Metals in Topsoil of Agricultural Land from an Agate Dyeing Village - Haodong Wang; Ye Li; Jia Fu; Shanshan Feng; Quanguo Cheng; Jianbing Wei (Water, Air, & Soil Pollution, 2025)

The GLI3 may be involved in the damage process of Eimeria tenella to chicken cecal tissue - Wanjiang Xiang; Ying Chen; Ye He; Yongmei Yu; Ping Li; Bi Wang; Zhentao Cheng (Veterinary Parasitology, 2025)

Combinative dual-nanoparticle assembly improves oxygen-autarky PDT efficacy in hypoxic tumors - Shengyu Liu; Yi Wang; Sijia Yao; Qian Li; Chenkai Sun; Yishan Chen; Junqiu Ye; Weisong Li; Dong Wu; Jianping Zhou; Hao Cheng; Yang Ding (Chemical Engineering Journal, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Responses of microbial community to different depths in volcanic soils of Nvshan Volcano - Jin Chen; Haining Wang; Ye Cui; Yiming Dai; Yueming Bao; Rui Qin; Qixiu Cheng; Xiaoyu Li (World Journal of Microbiology and Biotechnology, 2025)

The landscape of cell lineage tracing - Ye Feng; Guang Liu; Haiqing Li; Lin Cheng (Science China Life Sciences, 2025)

Different Expression Patterns and Interactions with Time Recorder DAL1 Revealed the Gene Expansion and Functional Differentiation of Flowering Integrator SOC1 During Larch Aging - Zha-Long Ye; Xiang-Yi Li; Dong-Xia Cheng; Wan-Feng Li (Journal of Plant Growth Regulation, 2025)

Tiered ecological risk assessment of perfluoroalkyl acid mixtures based on relative potency factor and species sensitivity distribution - Jianming Jiang; Xun Wang; Xi-Long Zhang; Hui Liu; Wen-Jun Hong; Minjie Li; Liang-Hong Guo; Cheng Ye; Hai-Wei Luo (Environmental Geochemistry and Health, 2025)

Mineral types dominate microbiomes and biogeochemical cycling in acid mine drainage - Ye Huang; Xiu-Tong Li; Zhen Jiang; Zong-Ling Liang; Wan Liu; Zheng-Hua Liu; Liang-Zhi Li; Zhen-Ni Yang; Guo-Qing Zhang; Hua-Qun Yin; Jie-Liang Liang; Nan Zhou; et al. (Water Research, 2025)

Optimized feeding schemes of heterotrophic anodic denitrification coupled with cathodic phosphate recovery from wastewater using a microbial fuel cell - Yuanyao Ye; Xueyi Yan; Yuanshou Jiang; Songlin Wang; Dongqi Liu; Yongzheng Ren; Daosheng Li; Huu Hao Ngo; Wenshan Guo; Dongle Cheng; Wei Jiang (Science of The Total Environment, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

The spatial network structure of the U.S. outdoor recreation economy and its influencing factors - Zhang Youyin; Yang Yaoyu; Liu Wenting; Jiang Yiyi; Xu Haibin; Qin Mingjie; Ye Chenghao; Zhang Yi; Li Tian; Tao Yingze; Cheng Di (Journal of Outdoor Recreation and Tourism, 2025)

Physiological responses and adaptive mechanisms of the harmful algal bloom species Heterosigma akashiwo to naphthalene exposure - Dan Huang; Hao-Yun Zhang; Hua-Jun Wang; Hong-Jia Huang; Shuang Liu; Chu-Yi Qiu; Cai-Qin Cheng; Yun Huang; Zhaohe Luo; Wei-Dong Yang; Hong-Ye Li; Xiao-Fei Zheng; et al. (Journal of Hazardous Materials, 2025)

Atomevo-odor: A database for understanding olfactory receptor-odorant pairs with multi-artificial intelligence methods - Heng-Yun Zhao; Si-Min Xu; Si-Nuo Xie; Wan-Lin Ye; Jian Li; Lang-Hong Wang; Shi-Lin Cao; Jun-Hu Cheng; Xin-An Zeng; Ji Ma (Food Chemistry, 2025)

Sensitive lateral flow immunoassay enabled by signal amplification strategy with high active oxidase-like nanozymes - Jie Zhu; Yunhui Cheng; Xufeng Wang; Hao Wu; Ye Jiao; Keyu Xing; Li Yao; Pei Jia; Zhou Xu (Food Bioscience, 2025)

Targeted amino acid metabolomic profiling revealed light-mediated quality variations in pink Auricularia cornea - Lei Ye; Lingzi Zhang; Jie Cheng; Wei Tan; Xiaolin Li; Xiaoping Zhang (Food Bioscience, 2025)

Fate of myofibrillar protein-bound Nε-(carboxymethyl)lysine in the presence of the human colonic microbiota after gastrointestinal digestion - Shuqi Hao; Zeyu Lu; Mengyu Ye; Na Li; Jiayi Hu; Wei Quan; Jiwen Cheng; Huaide Xu; Mei Li (Food Bioscience, 2025)

Key role of recycled terrigenous sediments in generating continental arc magmatism in the West Qinling orogen, China - Li-Tao Ma; Li-Qun Dai; Hao Liang; Ye-Dan Hu; Qing-Cheng Yang; Zi-Fu Zhao; Guo-Chao Sun (Chemical Geology, 2025)

Vertical distribution and seasonal variations of dicarboxylic acids in urban PM2.5: Insights from multi-level observations on 600 m Canton tower in Guangzhou - Dian Ye; Shengzhen Zhou; Yuxuan Liang; Chunlei Cheng; Chenglei Pei; Yao Li; Min Gao; Xijing Sun; Siqi Chen; Jian Hang; Pingqing Fu; Shaojia Fan (Atmospheric Environment, 2025)

A novel piperine derivative HJ-23 exhibits anti-colorectal cancer effects by activating the p53 pathway - Meiqi Zhang; Ruotong Liu; Wentao Jiang; Hanxue Li; Siyi Zhang; Wenhao Cheng; Xiaoqing Ye; Jingliang He; Yuanyuan Liu; Aixin Jing; Yizhuo Song; Dan Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Sterilization of Channel Catfish (Ictalurus punctatus) via Overexpression of bax Gene Regulated by a Tet-off System in the Primordial Germ Cells - Zhi Ye; Ahmed Elaswad; Guyu Qin; Dongdong Zhang; Baofeng Su; Karim Khalil; Zhenkui Qin; Nermeen Y. Abass; Qi Cheng; Ramjie Odin; Khoi Vo; Nathan Backenstose; et al. (Marine Biotechnology, 2025)

Transcriptomic insights into methanol utilization in Pichia pastoris lacking AOX genes under co-feeding conditions - Xueyun Zheng; Zhifang Ye; Jiao Gao; Yuechuo Hao; Cheng Li; Hongsen Xie; Ying Lin; Shuli Liang (Archives of Microbiology, 2025)

Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)
Laminated Diatom Mats (LDMs) in the low-latitude Western Pacific provide key insights into global climate and carbon cycling. While Ethmodiscus rex ( E. rex ) LDMs research has advanced, two critical aspects remain to be elucidated: (1) the precise chronology of LDMs formation, and (2) its relationship with oceanic circulation patterns and associated nutrient flux variations. In this study, we employed AMS 14 C dating coupled with carbonate content variations to constrain the formation age of LDMs, complemented by comprehensive geochemical and clay mineral analyses of core E20, we found: (1) Diatom blooms occurred mainly from Last Glacial Maximum (LGM) to early Holocene; (2) Sediments are mostly volcanic, with increased material in E. rex layers suggesting stronger deep currents transported volcanic debris; (3) Blooms weren’t solely caused by Asian dust-derived nutrients. We propose deep current intensification and topographic upwelling drove diatom growth, highlighting deep ocean processes’ role in surface productivity and LDMs formation. This advances understanding of their climate and carbon cycle significance.

Atmospheric nitrogen deposition has minor impacts on the abundance and diversity of arbuscular mycorrhizal fungi and their contribution to soil carbon stock in tropical forests - Andi Li; Peter Meidl; Senhao Wang; Bo Tang; Matthias C. Rillig; Guangcan Yu; Jing Chen; Rongzhen Liu; Zhiyang Lie; Anchi Wu; Lili Rong; Cheng Peng; et al. (Soil Biology and Biochemistry, 2025)

Prevalence of hypervirulent Klebsiella pneumoniae and application of the novel Klebsiella phage vB_KpnP_D39 for biocontrol of serotypes K1, K2, and K57 in prepared food-related samples - Diwei Zhang; Rui Jiao; Bin Cheng; Xiyan Zhang; Hanfang Chen; Hui Li; Xiangyu Cheng; Na Ling; Yingwang Ye (International Journal of Food Microbiology, 2025)

Improving XCO2 retrieval under high aerosol loads with fused satellite aerosol Data: Advancing understanding of anthropogenic emissions - Hao Zhu; Tianhai Cheng; Xingyu Li; Xiaotong Ye; Donghao Fan; Tao Tang; Haoran Tong; Lili Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Metal coordination-based double-network microsphere scaffolds facilitate bone regeneration via oxygen-driven mitochondrial oxidative phosphorylation - Chao Lin; Jialei He; Jiachen Li; Qingsong Zou; Lina Huang; Nuo Chen; Xiaojian Ye; Xiaoxiao Li; Wenguo Cui; Qian Cheng (Chemical Engineering Journal, 2025)

Thermoelectric performance in Ag2Se nanocomposites: The role of interstitial Ag and Pb orbital hybridization - Khak Ho Lim; Yuxuan Xia; Lixiang Xu; Mingjun Zhao; Mingquan Li; Ye Cheng; Jiale Mao; Shuang Wang; Lei Chen; Sai Wing Tsang; Pingwei Liu; Qingyue Wang; et al. (Chemical Engineering Journal, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Thickness-dependent topological phases and flat bands in rhombohedral multilayer graphene - Hanbo Xiao; Cheng Chen; Xin Sui; Shihao Zhang; Mengzhao Sun; Han Gao; Qi Jiang; Qiao Li; Lexian Yang; Mao Ye; Fangyuan Zhu; Meixiao Wang; et al. (Science Bulletin, 2025)

VvABF5 promotes ABA-mediated chlorophyll degradation by transcriptional activation of VvSGR during rachis browning of grape - Zhiqian Li; Dongfang Zou; Changjiang Nie; Xing Chen; Chang He; Xianbo Zheng; Bin Tan; Jun Cheng; Wei Wang; Pedro Martínez Gómez; Xia Ye; Jiancan Feng (Postharvest Biology and Technology, 2025)

Glycine betaine enhances heavy metal phytoremediation via rhizosphere modulation and nitrogen metabolism in king grass-Serratia marcescens strain S27 symbiosis - Miaomiao Wang; Xiaoyan Sun; Dandan Ye; Yali Duan; Dong Li; Yuanyuan Guo; Meng Wang; Yanmeng Huang; Feifei Chen; Huiping Feng; Xuezhi Dong; Shaoqi Cheng; et al. (Journal of Hazardous Materials, 2025)

Visualizing the spatial distribution of metabolites in tomato fruit at different maturity stages by matrix-assisted laser desorption/ionization mass spectrometry imaging - Sihui Guan; Chaochao Liu; Zhuping Yao; Chenxu Liu; Meiying Ruan; Rongqing Wang; Qingjing Ye; Hongjian Wan; Zhimiao Li; Guozhi Zhou; Ming Diao; Yuan Cheng (Food Research International, 2025)

Magnetic graphene-enhanced exonuclease III assisted amplification strategy driven carbon nanozyme for tri-mode detection of Escherichia coli O157:H7 - Yuwei Ren; Lulu Cao; Zongyang Li; Xin Zhang; Hui Li; Rui Jiao; Xiaoyu Yu; Zhao Liang; Ganghui Li; Xiyang Xia; Na Ling; Danfeng Zhang; et al. (Food Chemistry, 2025)

Deleted in malignant brain tumors 1 (DMBT1) gene relate to immune priming and phagocytosis modulation in the small abalone Haliotis diversicolor - Tuo Yao; Junyuan Tan; Jie Lu; Shengli Fu; Zhilv Xie; Bing Li; Changhong Cheng; Lingtong Ye (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Preparation of high-performance SiOx anode materials via dual interfacial reinforcement strategy - Ye Wang; Chong Xu; Junjie Fu; Sai Che; Guang Ma; Kaiyi Chen; Jiahao Yang; Shuang Liu; Gong Cheng; Dongyuan Zhang; Yunen Huang; Wenyue Gao; et al. (Chemical Engineering Journal, 2025)

First satellite observation of total column water vapor from the Chinese Environmental Trace Gases Monitoring Instrument - Ran Zhao; Chengxin Zhang; Wenjing Su; Jin Ye; Ziwei Li; Cheng Liu (Science China Earth Sciences, 2025)

PpSPL1 and PpSPL15 inhibit peach branching by increasing strigolactone synthesis - Wan Pei; Jie Zhang; Ruixian Shen; Hefang Xie; Yajia Zhang; Junjie Zhang; Xiaodong Lian; Haipeng Zhang; Nan Hou; Lei Wang; Xianbo Zheng; Jun Cheng; et al. (Planta, 2025)

Thermal deformation analysis of the Advanced Space-Based Solar Observatory (ASO-S) in orbit based on payloads measurement - Zhongguang Yang; Lei Deng; Cheng Zhu; Zengshan Yin; Tao He; Yu Huang; Yanping Bai; Hu Jiang; Yong Yang; Ye Zhang; Binglong Chen; Xinyu Li; et al. (Advances in Space Research, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Corrigendum to Impact of satellite AOD data on top-down estimation of biomass burning particulate matter emission [Sci. Total Environ. 864 (2023)/161055] - Xiaotong Ye; Tianhai Cheng; Xiaoyang Li; Hao Zhu (Science of The Total Environment, 2025)

Enhancing sulfate reduction in microbial electrolysis cells: The impact of intermittent electric field and extreme conditions on reaction mechanisms and functional genes - Zhibin Xia; Liang Qiao; Fei Chen; Xu Jiang; Pingting Li; Xing Zong; Yihan Wang; Feihong Wang; Luyan Zhang; Xiaolong Bai; Ye Yuan; Tianming Chen; et al. (Journal of Water Process Engineering, 2025)

Corrigendum to “Glycine betaine enhances heavy metal phytoremediation via rhizosphere modulation and nitrogen metabolism in king grass-Serratia marcescens strain S27 symbiosis” [J Hazard Mater 487 (2025) 137153] - Miaomiao Wang; Xiaoyan Sun; Dandan Ye; Yali Duan; Dong Li; Yuanyuan Guo; Meng Wang; Yanmeng Huang; Feifei Chen; Huiping Feng; Xuezhi Dong; Shaoqi Cheng; et al. (Journal of Hazardous Materials, 2025)

Mechanisms of starchy foods glycemic index reduction under different means and their impacts on food sensory qualities: A review - Yujie Zhang; Xingyu Mei; Wenqing Li; Yuxing Pan; Huan Cheng; Shiguo Chen; Xingqian Ye; Jianle Chen (Food Chemistry, 2025)

Assessing frozen flavor variations and process adaptability in peach (Prunus persica L. Batsch) cultivars based on molecular sensory technology - Zhongxin Li; Xinping Deng; Qian Zhao; Jin Chen; Yanyun Zhu; Xingqian Ye; Shiguo Chen; Huan Cheng (Food Bioscience, 2025)

Green fabrication of polyamide nanofiltration membranes with ultra-low chemical consumption by vacuum filtration-spraying assisted interfacial polymerization - Hong-Yu Fan; Cheng-Ye Zhu; Yu-Ren Xue; Jin-Bo Li; Chao Zhang; Tian-Yu Zhang; Li-Wu Fan; Zhi-Kang Xu (Desalination, 2025)

Recyclable and low-content deep eutectic solvent pretreatment at room temperature for fractionating uncondensed lignin and enhancing enzymatic saccharification - Cheng-Ye Ma; Qian Sun; Ling-Hua Xu; Haozhi Zhang; Jia-Long Wen; Zhenglong Li; Tong-Qi Yuan (Chemical Engineering Journal, 2025)

Environmental DNA/RNA metabarcoding for noninvasive and comprehensive monitoring and assessment of marine fishes - Peiyuan Ye; Jinping Cheng; Linus Shing Him Lo; Jingyu Liu; Chao Li; Kelvin Jun Yin So; Fei Xia; Meng Yan; Junjie Wang; Clara U; Jian-Wen Qiu; Wenlong Cai; et al. (Marine Pollution Bulletin, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Ni transformation and hydrochar properties during hydrothermal carbonization of cellulose - Peng Zhao; Shijie Yu; Ye Shui Zhang; Heng Cheng; Xiaoxiao Yang; Qinghai Li; Yanguo Zhang; Hui Zhou (Fuel, 2025)

Enhancing walnut butter with a pea protein isolate-pectin-pterostilbene complex: Physicochemical properties and stability analysis - Zonghui Tang; Panchen Fang; Yuting Tao; Qiuye Huang; Xuefei Xu; Xiaoyan Cheng; Faraz Hussain; Xueling Li; Jin Liang; Shuming Ye; Yue Sun (Food Research International, 2025)

Revealing the off-flavors in hydro-distilled essential oils of sweet orange (Citrus sinensis) by flavoromics strategy and computational simulation - Qian Zhao; Zhongxin Li; Keer Zhang; Xinping Deng; Guangnan Wang; Zhiyue Ye; Mingqi Liu; Jianle Chen; Shiguo Chen; Xingqian Ye; Huan Cheng (Food Chemistry, 2025)

Multiscale volumetric deformation in compacted bentonite triggered by anisotropic crystalline swelling - Wen-jie Dai; Yong-gui Chen; Yu-cheng Li; Wei-min Ye; Qiong Wang; Zhen-yu Yin (Engineering Geology, 2025)

Corrigendum to “Mechanism of charge self-reversal nano-nutrient delivery system to overcome the mucosal barrier” [Chem. Eng. J. 499 (2024) 155594] - Yaqing Bian; Tongliang Yang; Zihan Qu; Tiantian Zhang; Cheng Yang; Guiyun Chen; Ye Chen; Shuhong Li (Chemical Engineering Journal, 2025)

Redox-copolymer-enhanced electrochemical catalysis membrane for efficient water decontamination - Zhen Qiu; Cheng Chen; Xin Zeng; Guanda Shen; Qisheng Ye; Hailu Fu; Yongfu Li; Bing Yu (Chemical Engineering Journal, 2025)

Application of 18β-glycyrrhetinic acid in the structural modification of natural products: a review - Wan-Xin Li; Ye-Fang Lu; Fei Wang; Bing Ai; Sheng-Bo Jin; Siqi Li; Guang-Hua Xu; Cheng-Hua Jin (Molecular Diversity, 2025)

Enhanced biodegradation of glyphosate by Chlorella sorokiniana engineered with exogenous purple acid phosphatase - Si-Fen Liu; Zhong-Chen Yi; Zi-Qiong Huang; Zhen-Dong Yuan; Yu-Cheng Yang; Yongteng Zhao; Qing-Yu He; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Water Research, 2025)

Application of electroencephalogram (EEG) in the study of the influence of different contents of alcohol and Baijiu on brain perception - Guangnan Wang; Xiaolei Wang; Huan Cheng; Hehe Li; Zihan Qin; Fuping Zheng; Xingqian Ye; Baoguo Sun (Food Chemistry, 2025)

A “two birds one stone” strategy for self-healing marine coatings with antifouling and anticorrosion properties - Yong-Yin Cui; Tian-Cheng Chen; Jia-Ming Zhai; Ying Liu; Ye-Pin Gu; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2025)

Advances in polysaccharide-based conductive hydrogel for flexible electronics - Yiying Liu; Simian Fu; Kaiming Jin; Yugui Cheng; Yiqi Li; Yunjun Zhao; Ruonan Liu; Ye Tian (Carbohydrate Polymers, 2025)

Unlocking ABA’s role in rice cold tolerance: insights from Zhonghua 11 and Kasalath - Wenyu Li; Xin Lou; Zhijun Wang; Di Zhang; Lingling Li; Xiaoping Ding; Gongye Cheng; Weiying Nie; Zhilin Li; Jianghui Yu; Jiwai He; Nenghui Ye; et al. (Theoretical and Applied Genetics, 2025)

An investigation of aggregate breakup of structured soft clay under one-dimensional compression based on FESEM images - Chao Ye; Qian Cheng; Hong Sun; Fujun Niu; Yue Li (Bulletin of Engineering Geology and the Environment, 2025)

Characterization and mechanism of phthalic acid esters bioaccumulation in dominant mangrove fish at different habitats in the mangrove ecosystem of Dongzhai Harbor, China - Siwen Chen; Cheng Liu; Yuyan Liu; Jianan Liu; Zefeng Wang; Haofeng Liu; Ye Li; Min Liu (Science of The Total Environment, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Source-oriented health risk assessment and priority control factor analysis of heavy metals in urban soil of Shanghai - Cheng Shen; Shenfa Huang; Min Wang; Jian Wu; Jinghua Su; Kuangfei Lin; Xiurong Chen; Tianhao He; Ye Li; Chenyan Sha; Min Liu (Journal of Hazardous Materials, 2024)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Comprehensive analysis of risk factors (methanol, acetaldehyde and higher alcohols) in alcoholic beverages and their reduction strategies: GC–MS analysis and modified activated carbon adsorption and characterization - Ziyang Wu; Silei Lv; Peng Xiao; Gert IJ. Salentijn; Huan Cheng; Hehe Li; Jinyuan Sun; Xingqian Ye; Baoguo Sun (Food Chemistry, 2024)

Machine learning phenotyping and GWAS reveal genetic basis of Cd tolerance and absorption in jute - Zemao Yang; Alei Li; Jiquan Chen; Zhigang Dai; Jianguang Su; Canhui Deng; Gaoao Ye; Chaohua Cheng; Qing Tang; Xiaoyu Zhang; Ying Xu; Xiaojun Chen; et al. (Environmental Pollution, 2024)

Multi-stimuli geminate encryption based on triphenylethylene for advanced anti-counterfeiting - Zhuo-Cheng Li; Zuo-Qin Liang; Zi-Hang Zhang; Su-Hang Xu; Pu Wang; Guo-Liang Dai; Chang-Qing Ye; Xiao-Mei Wang (Chemical Engineering Journal, 2024)

Soil microbial community dynamics and contribution to litter decomposition in two years in a Tibetan alpine forest along an elevational gradient - Zhuonan Hou; Xinjun Zhang; Ruihong Wang; Tiantian Ma; Xintong Li; Su Chang; Yanying Han; Meidi Cheng; Jie Lu; Bo Wang; Yanhui Ye; Yuquan Wei (CATENA, 2024)

Preoperative versus postoperative nonsteroidal anti-inflammatory drugs in femoroacetabular impingement patients undergoing hip arthroscopy surgery: analgesic effect, joint function, patients’ satisfaction, and quality of life - Zhiyuan Guo; Guangfei Liu; Weibin Li; Shouliang Lu; Ye Zhao; Lu Wang; Cai Cheng (Inflammopharmacology, 2024)

Extracting hydromechanical properties of montmorillonite quasi-crystals via nanoindentation of oriented thin films - Yu-Cheng Li; Yong-Gui Chen; Li Liu; Guo-Ping Zhang; Wei-Min Ye; Qiong Wang (Applied Clay Science, 2024)

TROPOMI unravels transboundary transport pathways of atmospheric carbon monoxide in Tibetan Plateau - Peize Lin; Yuan Tian; Tobias Borsdorff; Zhiwei Li; Jochen Landgraf; Hongyu Wu; Jingkai Xue; Dake Ding; Hang Ye; Yizhi Zhu; Cheng Liu (Science of The Total Environment, 2024)

Pyrrole adducts mediated mitochondrial dysfunction activates SARM1-dependent axon degeneration in 2,5-hexanedione-induced neuropathy - Wenting Ni; Yihan Ye; Shuai Wang; Xianjie Li; Hui Li; Dong Cheng; Qiang Jia; Zhidan Liu; Shulin Shan; Yalong Qiang; Shihua Chao; Xiulan Zhao; et al. (Environmental Pollution, 2024)

Study on the effects of electrode volume fraction and electrode particle radius on dynamic electrochemical-thermal-aging coupling characteristics of lithium cell based on cylindrical cell design method - Xu-Dong Yuan; Zhen-Kai Xiong; Lian-Cheng Li; Chuan-Ye Tang; Qi-Wei Jia; Hong-Chuan Tuo; Yan Zhang (Chemical Engineering Journal, 2024)

Preparation of microstructure controllable CL-20/FOX-7 composite microspheres by microchannel recrystallization technology to enhance safety and combustion performance - Wenqing Li; Shimin Zhang; Songchao Shi; Xiaoying Cheng; Chongwei An; Jingyu Wang; Baoyun Ye (Chemical Engineering Journal, 2024)

Asymmetric structural strategy enables efficient MR-TADF emitters with low efficiency roll-off and doping-concentration insensitivity - Zhang-Li Cheng; Jie Li; Hui Wang; Feng Huang; Ying-Chun Cheng; Hao Wu; Xin Xiong; Tong-Yuan Zhang; Jia Yu; Jun Ye; Kai Wang; Xiao-Hong Zhang (Chemical Engineering Journal, 2024)

Mechanism of charge self-reversal nano-nutrient delivery system to overcome the mucosal barrier - Yaqing Bian; Tongliang Yang; Zihan Qu; Tiantian Zhang; Cheng Yang; Guiyun Chen; Ye Chen; Shuhong Li (Chemical Engineering Journal, 2024)

Salinomycin, a potent inhibitor of XOD and URAT1, ameliorates hyperuricemic nephropathy by activating NRF2, modulating the gut microbiota, and promoting SCFA production - Yong-jun Chen; Zi-tao Guo; Hai-qiao Chen; Shi-fan Zhang; Ying-xia Bao; Zhoufan Xie; Jia-le Ke; Wen-jie Ye; Jia-cheng Liang; Jia-chen Chen; Ning Li; Feng-xin Zheng; et al. (Chemico-Biological Interactions, 2024)

Study on Elastoplastic Damage Constitutive Model and Permeability Evolution Law of Gas-Bearing Coal - Jiale Fu; Bobo Li; Chonghong Ren; Qiaoyun Cheng; Pingping Ye; Sandong Zhou (Rock Mechanics and Rock Engineering, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

TaSRT2 recognizes a viral protein to activate host immunity by increasing histone acetylation - Kaili Zhong; Yaoyao Jiang; Haichao Hu; Bowen Yuan; Mila Wu; Aizhu Tu; Gecheng Xu; Linna Cai; Tingting Liu; Shiqi Gao; Linzhi Li; Qiansheng Liao; et al. (Science Bulletin, 2024)

Deciphering the pivotal material properties of perovskite for hydrogen production in tar catalytic cracking - Wang-mi Chen; Bei-dou Xi; Mei-ying Ye; Ming-xiao Li; Jia-qi Hou; Yu-fang Wei; Cheng-ze Yu; Fan-hua Meng (Fuel, 2024)

A novel LD-targeting cysteine-activated fluorescent probe for diagnosis of APAP-induced liver injury and its application in food analysis - Zhiqiang Yang; Xin Kang; Jia Li; Longxuan Li; Xiaoping Ye; Xiaoya Liu; Kun Chen; Yun Deng; Cheng Peng; Bo Ren; Zhixing Cao; Yuyu Fang (Food Chemistry, 2024)

Chronic PM2.5 exposure disrupts intestinal barrier integrity via microbial dysbiosis-triggered TLR2/5-MyD88-NLRP3 inflammasome activation - Zihan Ran; Jingcheng Yang; Liang Liu; Shaobo Wu; YanPeng An; Wanwan Hou; Tianyuan Cheng; Youyi Zhang; Yiqing Zhang; Yechao Huang; Qianyue Zhang; Jiaping Wan; et al. (Environmental Research, 2024)

Chrysalis-inspired high-toughness low-modulus conductive hydrogel sensor for intelligent sensing - Yugui Cheng; Simian Fu; Kaiming Jin; Yiying Liu; Jingtong Ma; Deliang Li; Qingying Lyu; Yehan Li; Xiaoyang Jiang; Ruonan Liu; Ye Tian (Chemical Engineering Journal, 2024)

Correction to: Deletion of Luzp2 Does Not Cause Hearing Loss in Mice - Cheng Cheng; Guangjie Zhu; Kaijian Wang; Chuan Bu; Siyu Li; Yue Qiu; Jie Lu; Xinya Ji; Wenli Hao; Junguo Wang; Chengwen Zhu; Ye Yang; et al. (Neuroscience Bulletin, 2024)

Deletion of Luzp2 Does Not Cause Hearing Loss in Mice - Cheng Cheng; Guangjie Zhu; Kaijian Wang; Chuan Bu; Siyu Li; Yue Qiu; Jie Lu; Xinya Ji; Wenli Hao; Junguo Wang; Chengwen Zhu; Ye Yang; et al. (Neuroscience Bulletin, 2024)

Analysis of histomorphology and SERNINA5 gene expression in different regions of epididymis of cattleyak - Haiyan Li; Cheng Pan; Yifei Wang; Jingjing Li; Zhenzhen Zhang; Khuram Shahzad; Shehr Bano Mustafa; Ye Wang; Wangsheng Zhao (Journal of Molecular Histology, 2024)

Organophosphorus flame retardants in the Qiantang River of China: occurrence, source and ecological risk assessment - Wen-Jun Hong; Xi-Long Zhang; Hui Liu; Jian-Ming Jiang; Xun Wang; Minjie Li; Liang-Hong Guo; Cheng Ye; Hai-Gang Wu (Environmental Geochemistry and Health, 2024)

Natural harmaline acts as novel fluorescent probe for hypochlorous acid and promising therapeutic candidate for rheumatoid arthritis - Dongbin Zheng; Yi Zuo; Longxuan Li; Arlene McDowell; Yuening Cao; Xiaoping Ye; Houcheng Zhou; Cheng Peng; Yun Deng; Jun Lu; Yuyu Fang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Rapid and non-destructive identification of Panax ginseng origins using hyperspectral imaging, visible light imaging, and X-ray imaging combined with multi-source data fusion strategies - Jiacong Ping; Zehua Ying; Nan Hao; Peiqi Miao; Cheng Ye; Changqing Liu; Wenlong Li (Food Research International, 2024)

Optimisation and characterisation of KOH-activated carbon obtained from Baijiu spent grains for the mitigation of risk factors in alcoholic beverages - Ziyang Wu; Silei Lv; Peng Xiao; Xiuxiu Yin; Huan Cheng; Hehe Li; Jinyuan Sun; Xingqian Ye; Mingquan Huang; Fuping Zheng; Baoguo Sun (Food Chemistry, 2024)

Fast and robust potassium storage enabled by controllable hierarchical CoTe2/MoS2@C nanorods with semi-coherent heterogeneous interfaces - Yukun Zhang; Xinhong Zhao; Weizhe Liu; Zhiqiang Zheng; Zhanghua Fu; JiaJia Ye; Huancai Li; Cheng Hu (Chemical Engineering Journal, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Machine learning-based prediction of cadmium pollution in topsoil and identification of critical driving factors in a mining area - Cheng Li; Zhongcheng Jiang; Wenli Li; Tao Yu; Xiangke Wu; Zhaoxin Hu; Yeyu Yang; Zhongfang Yang; Haofan Xu; Wenping Zhang; Wenjie Zhang; Zongda Ye (Environmental Geochemistry and Health, 2024)

Single and combined effects of high-fat diet and ammonia nitrogen on oxidative stress, lipid accumulation and inflammation in liver of grass carp Ctenopharyngodon idella - Cheng Zhang; Wenhao Huang; Xiaotian Zhang; Pengju Li; Chi Wang; Limin Ye; Zhongzheng Xu; Julin Yuan; Haibo Yu (Aquaculture, 2024)

Quantifying instantaneous nitrogen oxides emissions from power plants based on space observations - Tao Tang; Tianhai Cheng; Hao Zhu; Xiaotong Ye; Donghao Fan; Xingyu Li; Haoran Tong (Science of The Total Environment, 2024)

Frequency-modulated alternating current-driven bioelectrodes for enhanced mineralization of Alizarin Yellow R - Ye Yuan; Junjie Zhang; Lulu Zhang; Wanxin Yin; Shihan Zhang; Tianming Chen; Zhaoxia Li; Cheng Ding; Haoyi Cheng; Aijie Wang; Fan Chen (Journal of Hazardous Materials, 2024)

Optimal emission control plan aiming to basically eliminate PM2.5 heavy pollution in North and Northwest China in 2018 - Zhilan Ye; Long Cheng; Jie Li; Fei Pan; Wenyi Yang; Xueshun Chen; Huiyun Du; Tao Wang; Zhe Wang; Zifa Wang (Journal of Cleaner Production, 2024)

Periodic inundation accelerates the release process of organic carbon from plant litter - Zhonghang Wu; Mao Ye; Ran Li; Jingjie Feng; Hang Wan; Xiaolong Cheng (Journal of Environmental Management, 2024)

Incomplete solid fuel burning as the major emission source of atmospheric phenols and environmentally persistent free radicals - Anyuan Cheng; Yang Li; Di Wu; Zihua Guo; Yi Su; Xiang Ding; Xiu Chen; Yuankai Shao; Qingcai Chen; Weihua Song; Xingnan Ye; Jianmin Chen; et al. (Fuel, 2024)

Enhancing the stability of zein pickering foams via hydrophilic reassembly with sugar alcohols and glycosides: A structural and molecular investigation - Zihan Qu; Guiyun Chen; Tongliang Yang; Fushen Niu; Yaqing Bian; Cheng Yang; Ye Chen; Shuhong Li (Food Hydrocolloids, 2024)

Strategic assembly of active phases on Co-Fe bimetallic catalysts for efficient Fischer-Tropsch synthesis - Yunhao Liu; Qingpeng Cheng; Shuaishuai Lyu; Xincheng Li; Song Song; Tong Ding; Ye Tian; Xingang Li (Chemical Engineering Journal, 2024)

Nanoscale assembly of MoS2/CoS2/Ni3S2 grown on Ni foam for synergistic capture of iodine - Chaonan Wang; Huiqin Yao; Jingtong Sun; Tian Tong; Zi Ye; Hongliang Dong; Cheng Li; Shulan Ma (Chemical Engineering Journal, 2024)

Intermittent electrostimulation-modified direct interspecies electron transfer for enhanced methanogenesis in anaerobic digestion of sulfate-rich wastewater - Ye Yuan; Huan Liu; Lulu Zhang; Wanxin Yin; Lin Li; Tianming Chen; Zhaoxia Li; Aijie Wang; Cheng Ding (Bioresource Technology, 2024)

Comparative pharmacokinetic investigation on crocetin in hyperlipidemia and normal rats after oral administration - Cheng-Ye She; Yuan-Xiong Deng; Qin-Yu Wu; Jing Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Ethanol Treated Mn–Zr Compound for Fluoride Removal and its Adsorption Mechanism - Yuanyao Ye; Xueyi Yan; Xi Li; Shijing Huang; Wei Jiang; Dongqi Liu; Yongzheng Ren; Dongle Cheng (International Journal of Environmental Research, 2024)

Effects of glycerol monolaurate on estradiol and follicle-stimulating hormones, offspring quality, and mRNA expression of reproductive-related genes of zebrafish (Danio rerio) females - Boyu Li; Limin Ye; Cheng Zhang; Ruofan Liu; Chi Wang; Xiaotian Zhang; Hong Ji; Haibo Yu (Fish Physiology and Biochemistry, 2024)

Multi‐omics analyses reveal the signatures of metabolite transfers across trophic levels in a high‐ CO 2 ocean - Mengcheng Ye; Jiale Zhang; Mengting Xiao; Jiali Huang; Yunyue Zhou; John Beardall; John A. Raven; Guang Gao; Xiao Liang; Fenghuang Wu; Baoyi Peng; Leyao Xu; et al. (Limnology and Oceanography, 2024)
Although the diverse impacts of elevated dissolved CO 2 and warming on organisms within various trophic levels in marine food webs are well documented, we have yet to explore the biological links across different levels of biological organization from primary producers to secondary producers on an evolutionary time scale in a high‐CO 2 ocean. Here, we cultured a model marine diatom Phaeodactylum tricornutum (primary producer) in predicted future high‐CO 2 and/or warming conditions for ~ 1250 d with an experimental evolution approach and then fed them to the clam Coelomactra antiquata (secondary producer). We present an in‐depth multi‐omics analysis along the methylome (primary producer)–transcriptome (primary producer)–metabolome (primary producer)–metabolome (secondary producer) continuum. Our results showed that the downregulated terpenoid backbone biosynthesis in the methylome and transcriptome lead to decreased pyruvate levels and upregulation of some pathways (such as phenylalanine metabolism) in the metabolome of the primary producer in the long‐term warming conditions. These changes in metabolomic profile in the primary producer were then transferred to the secondary producer, resulting in changes in abundance of some metabolites, such as decreases in pyruvate, and in pyruvaldhyde (also known as methylglyoxal), and increases in 2‐hydroxylamino‐4,6‐dinitrotoluene. Our study provides a new insight into the molecular mechanisms underlying the trophic transfer from primary to secondary producers in a future high‐CO 2 ocean and may provide more accurate projections of marine ecosystem services and functions over the next century.

Establishment and characterization of the PDAC-X3 cell line: a novel Chinese-origin pancreatic ductal adenocarcinoma cell line - Changpeng Chai; Huan Tang; Xin Miao; Yuanhui Su; Lu Li; Cheng Yu; Jianfeng Yi; Zhenzhen Ye; Long Miao; Bo Zhang; Zhengfeng Wang; Wei Luo; et al. (Human Cell, 2024)

Rapid detection of multiple phytoplasmas with an All-In-One Dual (AIOD) CRISPR assay - Qicheng Li; Sicheng Guo; Jidong Li; Jian Jiao; Qiqi Yang; Jia Yao; Yun Chen; Xia Ye; Jun Cheng; Bin Tan; Xianbo Zheng; Yingxia Wu; et al. (Crop Protection, 2024)

Overexpression of the grape β-galactosidase gene VvBGAL3 delays the softening and extends the shelf life of tomato fruits - Shanshan He; Hongli Wei; Zhirui Xue; Meng Li; Jiannan Xie; Jiakang Qian; Xing Chen; Zhiqian Li; Chang He; Bin Tan; Xianbo Zheng; Jun Cheng; et al. (Postharvest Biology and Technology, 2024)

Two birds with one stone: Co/Fe bi-MOFs@PAN nanofiber aerogel films for efficient degradation of organic contaminants and separation of emulsions - Guojun Jiang; Yue Qi; Liying Qian; Wei Li; Yeting Gao; Yuchen Chen; Yujian Cheng; Xinjie Ying; Sheng Xie; Sai Zhang; Xiangyu Ye (Journal of Water Process Engineering, 2024)

A macroscopic model for predicating stepwise crystalline swelling of montmorillonite - Wen-jie Dai; Yong-gui Chen; Yu-cheng Li; Wei-min Ye; Qiong Wang (Computers and Geotechnics, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

A rapid and efficient Agrobacterium-mediated transient transformation system in grape berries - Jiannan Xie; Chang He; Zhiqian Li; Meng Li; Shanshan He; Jiakang Qian; Bin Tan; Xianbo Zheng; Jun Cheng; Wei Wang; Jidong Li; Jiancan Feng; et al. (Protoplasma, 2024)

A Monte Carlo simulation-based health risk assessment of heavy metals in soils of the tropical region in southern China - Haoran Huang; Hang Su; Xiang Li; Yan Li; Yujie Jiang; Ke Liu; Xuefeng Xie; Zhenyi Jia; Huanchao Zhang; Genmei Wang; Zi Ye; Xinyu Cheng; et al. (Environmental Geochemistry and Health, 2024)

Graph Laplace Regularization-based pressure sensor placement strategy for leak localization in the water distribution networks under joint hydraulic and topological feature spaces - Menglong Cheng; Juan Li; Chunyue Wang; Chaoxiong Ye; Zheng Chang (Water Research, 2024)

Paeonol can improve hypoxic-induced H9c2 cells injury and ion channel activity by up-regulating the expression of CKIP-1 - Xinran Li; Hesheng Hu; Jie Yin; Wenjuan Cheng; Yugen Shi; Ye Wang (Tissue and Cell, 2024)

Ultrathin Sn-doped Ga2O3 for power field-effect transistors: Si-compatible 4-inch array with high-k gate dielectric - Zi-Chun Liu; Jia-Cheng Li; Hui-Xia Yang; Han Yang; Yuan Huang; Yi-Yun Zhang; Pui-To Lai; Yuan-Xiao Ma; Ye-Liang Wang (Science Bulletin, 2024)

Syn- and post-collisional mafic igneous rocks from the East Kunlun Orogenic Belt: Implications for recycling of subducting continental crust during the Silurian-Devonian - Li-Tao Ma; Guo-Chao Sun; Li-Qun Dai; Zi-Fu Zhao; Ye-Dan Hu; Qing-Cheng Yang; Lei Qin; Bing Gong (Lithos, 2024)

Absorption characteristics and molecular mechanism of a low viscosity iron-based ionic liquid for removing H2S - Zhonghao Li; Zhou Feng; Hongwei Jin; Kangkang Li; Hongzhi Xia; Shiqi Qu; Sujuan Ye; Huanong Cheng; Qingli Wei; Yugang Li; Xinshun Tan; Shiqing Zheng (Journal of Environmental Chemical Engineering, 2024)

Increasing biohydrogen production from swine wastewater influenced by anaerobic consortium and nickel ferrite nanoparticles - Jing Ye; Lihua Yu; Juanjuan Cao; Pei Zhao; Qin Zhang; Yanbin Li; Cheng Qian; khadija EI Galai; Mengdie Gao; Xinyu Yang (Fuel, 2024)

The insightful water quality analysis and predictive model establishment via machine learning in dual-source drinking water distribution system - Huiping Li; Baiqin Zhou; Xiaoyan Xu; Ranran Huo; Ting Zhou; Xiaochen Dong; Cheng Ye; Tian Li; Li Xie; Weihai Pang (Environmental Research, 2024)

Radicals mediated polypropylene waste plastics oxidation into ketone fuel - Jingya Ye; Hengxin Liu; Wenjie Gao; Ning Li; Zhanjun Cheng; Beibei Yan; Guanyi Chen (Chemical Engineering Journal, 2024)

MYPT1SMKO Mice Function as a Novel Spontaneous Age- and Hypertension-Dependent Animal Model of CSVD - Jian Chen; Cheng-Gang Li; Li-Xuan Yang; Yi Qian; Li-Wen Zhu; Pin-Yi Liu; Xiang Cao; Ye Wang; Min-Sheng Zhu; Yun Xu (Translational Stroke Research, 2024)

Comparative proteomic and metabolomic analyses reveal stress responses of hemp to salinity - Yang Yang; Yu Cheng; Zhenhua Lu; Hailong Ye; Guanghui Du; Zheng Li (Plant Cell Reports, 2024)

Transcriptomic analysis reveals molecular characterization and immune landscape of PANoptosis-related genes in atherosclerosis - Zhipeng Zheng; Kaiyuan Li; Zhiyuan Yang; Xiaowen Wang; Cheng Shen; Yubin Zhang; Huimin Lu; Zhifeng Yin; Min Sha; Jun Ye; Li Zhu (Inflammation Research, 2024)

Swelling characteristics of compacted graphene-modified GMZ bentonite infiltrated with NaCl solution - Yu-Hao Hu; Yong-Gui Chen; Yu-Cheng Li; Wei-Min Ye; Qiong Wang; Dong-Bei Wu (Bulletin of Engineering Geology and the Environment, 2024)

Reference Intervals of Serum Iodine Concentration in Chinese Pregnant Women - Yi Wu; Huan-huan Long; Su-juan Zhang; Min-Min Li; Chao-gang Chen; Cheng Wang; Zheng-yu Sheng; Yan-bin Ye; Shu-yu Zuo; Wen-jing Pan; Zhao-min Liu (Biological Trace Element Research, 2024)

Selective breeding in the noble scallop (Chlamys nobilis) for low-temperature resistance to reduce overwintering losses - Chuanxu Zhang; Cheng He; Yizhou Sun; Hongkuan Zhang; Ting Ye; Faxin Liu; Hongyu Ma; Shengkang Li; Huaiping Zheng (Aquaculture, 2024)

Activation of RXRα exerts cardioprotection through transcriptional upregulation of Ndufs4 in heart failure - Mingyan Shao; Lingru Li; Lin Ma; Chao Song; Weili Li; Yawen Zhang; Wenkun Cheng; Yun Chen; Ye Yang; Qian Wang; Chun Li; Qi Wang; et al. (Science Bulletin, 2024)

Overexpressing peach PpePAO1 gene improves the nutrient value of tomato and enhances resistance against Botrytis cinerea - Zhenguo Cui; Yabo Jiang; Yang Chen; Xin Cheng; Bin Tan; Jun Cheng; Langlang Zhang; Xia Ye; Xiaobei Wang; Zhiqian Li; Xianbo Zheng; Jiancan Feng; et al. (Postharvest Biology and Technology, 2024)

Pressure-assisted hydrothermal pretreatment for biorefinery to enhance pulp production - Qian Sun; Bin Wang; Haijian Huang; Cheng-Ye Ma; Yanguang Ma; Xiaojun Shen; Xuefei Cao; Zhuohua Sun; Li Zhang; Tong-Qi Yuan (Chemical Engineering Journal, 2024)

Tuning combustion and energy in hydroxylammonium nitrate (HAN)-based electrically controlled solid propellant - Feng Li; Zhiwen Wang; Qianyi Zhang; Zeyu Cheng; Yixin Yu; Ruiqi Shen; Yinghua Ye; Luigi T. DeLuca; Wei Zhang (Chemical Engineering Journal, 2024)

Social parasitism behavior between two species of edible wasps in China - Cheng-Ye Wang; Hao-Yu Chen; Bing-Qing Fang; Pan-Li Yang; Zhao He; Long Sun; Jin Gan; Min Zhao; Ying Feng (Journal of Ethology, 2024)

Lactate induces C2C12 myoblasts differentiation by mediating ROS/p38 MAPK signalling pathway - Chunfang Cheng; Wenxi Li; Yuanqian Ye; Yuanjie Zhu; Mengyuan Tang; Zhihong Hu; Hu Su; Caixia Dang; Juan Wan; Zhibin Liu; Yanchun Gong; Li-Hua Yao (Tissue and Cell, 2024)

Characterization of organic vapors by a Vocus proton-transfer-reaction mass spectrometry at a mountain site in southeastern China - Yi Zhang; Weiqi Xu; Wei Zhou; Yan Li; Zijun Zhang; Aodong Du; Hongqin Qiao; Ye Kuang; Lanzhong Liu; Zhiqiang Zhang; Xiao He; Xueling Cheng; et al. (Science of The Total Environment, 2024)

Quantifying denudation rates and sediment recycling of low-relief, high-elevation landscapes using in-situ and meteoric cosmogenic nuclides - Ye Yang; Shun-Cheng Zhang; Jia-Xin Zhang; Li-Feng Cui; Cong-Qiang Liu; Sheng Xu (Geochimica et Cosmochimica Acta, 2024)

Characterization of the broad-spectrum phage vB_CsaM_CBT2 and its inhibition of multidrug-resistant Cronobacter sakazakii in powered infant formula - Bin Cheng; Diwei Zhang; Ting Wang; Hanfang Chen; Yuhang Wang; Yang Wang; Zongyang Li; Na Ling; Yingwang Ye (Food Control, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

A systemic study of cyenopyrafen in strawberry cultivation system: Efficacy, residue behavior, and impact on honeybees (Apis mellifera L.) - Hui Ye; Jinhua Jiang; Yuan Lei; Nan Fang; Yuqin Luo; Youpu Cheng; Yanjie Li; Xiangyun Wang; Hongmei He; Jianzhong Yu; Zhenlan Xu; Changpeng Zhang (Environmental Pollution, 2024)

In-situ electron capture by surface Co-Ci to facilitate the solar water splitting of Fe2O3 - Chang Li; Cheng Lu; Ye Zhu; Shuo Li; Yong Feng; Yiliu Yang; Bai Xu; Kun Feng; Jun Zhong (Chemical Engineering Journal, 2024)

Self-confining isolated chiral chromophore for circularly polarized organic afterglow from amorphous polymer systems - Chenyu Zhang; Xin Yan; Zhisheng Gao; He Cheng; Xin Zhang; Huanhuan Li; Runfeng Chen; Hui Li; Gaozhan Xie; Ye Tao (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Meta-analysis of the SARS-CoV-2 positivity rate in municipal wastewater - Keyi Cheng; Ye Lv; Chaokang Li; Shi Cheng; Shanshan Xu; Xin Gao; Hong Xu (Environmental Geochemistry and Health, 2024)

Xiashengella succiniciproducens gen. nov., sp. nov., a succinate-producing bacterium isolated from an anaerobic digestion tank in the family Marinilabiliaceae of the order Bacteroidales - Hao-Jie Huang; Xi Zhang; Xin-Wei Sun; Biao Chen; Xiu-Tong Li; Nan Zhou; Rashidin Abdugheni; Qiu-Yin Cheng; Tie-Jun Zhang; Yao Liu; Yong Jiang; Ye Deng; et al. (Archives of Microbiology, 2024)

Ship Shaft-Rate Electric Field Signal Denoising Method Based on VMD-MSS - Ye Wang; Dan Wang; Cheng Chi; Zhentao Yu; Jianwei Li; Lu Yu (Journal of Marine Science and Engineering, 2024)
The presence of complex electromagnetic noise in the ocean significantly impacts the accuracy of ship shaft-rate electric field signal detection, necessitating the development of an effective denoising method to enhance detection precision. Nevertheless, traditional denoising methods encounter issues like low frequency resolution, challenging threshold configuration, and mode mixing. This study introduces a method that integrates variational mode decomposition (VMD) with multi-window spectral subtraction (MSS). The intrinsic mode functions (IMFs) of noisy signals are extracted using VMD, and the noise components within different IMFs are identified. The spectral features of both signal and noise within different IMFs are leveraged to eliminate noise signals via MSS. Subsequently, the denoised components of IMFs are rearranged to derive the denoised ship shaft-rate electric field signals, achieving noise reduction across various frequency bands. Following validation using simulation signals and empirical data, the noise reduction efficacy of VMD-MSS surpasses that of alternative methods, demonstrating robust performance even at low signal-to-noise ratios. The marine electromagnetic noise is effectively suppressed in the empirical data, while preserving the characteristics of ship’s shaft-rate signals, thereby validating the method’s efficacy and demonstrating its practical engineering value.

Heterogeneous reactions significantly contribute to the atmospheric formation of nitrated aromatic compounds during the haze episode in urban Beijing - Zhen Cheng; Xinghua Qiu; Ailin Li; Qianqian Chai; Xiaodi Shi; Yanli Ge; Theodore K. Koenig; Yan Zheng; Shiyi Chen; Min Hu; Chunxiang Ye; Rico K.Y. Cheung; et al. (Science of The Total Environment, 2024)

ECM1 promotes migration and invasion in endometriosis - Chen Zhang; Hongyan Cheng; Xue Ye; Heng Cui; Yi Li; Honglan Zhu; Xiaohong Chang (Reproductive Biology, 2024)

IiAGL6 participates in the regulation of stamen development and pollen formation in Isatis indigotica - Liu Yang; Xin Qiao; Hao-En He; Wei-Wei Yi; Ya-Nan Gao; Xiao-Min Tan; Hao Cheng; Xiao-Fang Hou; Ye-Ye Ma; Hong-Li Wang; Xuan Huang; Yan-Qin Ma; et al. (Plant Science, 2024)

Characteristics of NOX and NH3 emissions from in-use heavy-duty diesel vehicles with various aftertreatment technologies in China - Liqiang He; Gang Li; Xiaomeng Wu; Shaojun Zhang; Miao Tian; Zhenhua Li; Cheng Huang; Qingyao Hu; Ye Wu; Jiming Hao (Journal of Hazardous Materials, 2024)

A multifunctional interface optimization strategy for efficient Quasi-2D blue perovskite Light-Emitting diodes - Yuliang Ye; Zhou Cui; Zunxian Yang; Zhiwei Zeng; Zongyi Meng; Hongyi Hong; Songwei Ye; Zhiming Cheng; Qianting Lan; Jiaxiang Wang; Ye Chen; Hui Zhang; et al. (Chemical Engineering Journal, 2024)

Long-term hourly air quality data bridging of neighboring sites using automated machine learning: A case study in the Greater Bay area of China - Boxi Wu; Cheng Wu; Yuchen Ye; Chenglei Pei; Tao Deng; Yong Jie Li; Xingcheng Lu; Lei Wang; Bin Hu; Mei Li; Dui Wu (Atmospheric Environment, 2024)

Hypoxia Potentiated Lung Cancer Cell Migration and Invasion by up-regulating HIF1α/JAK2/STAT3 Axis and Activating MMP13 Transcription - Xiaoju Cheng; Damin Liang; Xiaoqian Li; Chengmin Deng; Meng Ye; Jiao Yang; Yurui Liu; Kaifeng Wu; Jie Wu; Peng Tian (Cell Biochemistry and Biophysics, 2024)

Genomic sequencing revealed recombination event between clade 1 and clade 2 occurs in circulating varicella-zoster virus in China - Jia Li; Dan Wang; Libin Qi; Yuewu Yang; Jiawei Pei; Yangchao Dong; Yuan Wang; Min Yao; Fanglin Zhang; Yingfeng Lei; Linfeng Cheng; Wei Ye (Brazilian Journal of Microbiology, 2024)

Mechanistic insights into the effects of diuron exposure on Alexandrium pacificum - Dan Huang; Cai-Qin Cheng; Jiang-Bing Qiu; Yun Huang; Hao-Yun Zhang; Zhen-Hao Xu; Si-Wei Wu; Yi-Tong Huang; Jian Chen; Li-Gong Zou; Wei-Dong Yang; Xiao-Fei Zheng; et al. (Water Research, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

Co-exposure of nanoplastics and arsenic causes neurotoxicity in zebrafish (Danio rerio) through disrupting homeostasis of microbiota–intestine–brain axis - Cheng Zhang; Yanyao Li; Haibo Yu; Tian Li; Limin Ye; Xiaotian Zhang; Chi Wang; Pengju Li; Hong Ji; Qinfeng Gao; Shuanglin Dong (Science of The Total Environment, 2024)

Insights into the molecular network underlying phytotoxicity and phytoaccumulation of ciprofloxacin - Hai-Ming Zhao; He-Biao Huang; Zhen-Xuan Zhan; Yao-Yao Ye; Ji-Liang Cheng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Yunchang Xie; Ce-Hui Mo (Science of The Total Environment, 2024)

Decoding the key compounds responsible for the empty cup aroma of soy sauce aroma type baijiu - Dan Qin; Silei Lv; Yi Shen; Jie Shi; Yingli Jiang; Wei Cheng; Dongmei Wang; Hehe Li; Yanyan Zhang; Huan Cheng; Xingqian Ye; Baoguo Sun (Food Chemistry, 2024)

Bright photoactivatable probes based on triphenylethylene for Cu2+ detection in tap water and tea samples - Zuo-Qin Liang; Dong-Dong Song; Zhuo-Cheng Li; Su-Hang Xu; Guo-Liang Dai; Chang-Qing Ye; Xiao-Mei Wang; Xu-Tang Tao (Food Chemistry, 2024)

Simultaneous removal of organic micropollutants and metals from water by a multifunctional β-cyclodextrin polymer-supported-polyaniline composite - Pin Wang; Guangyu An; Peter Jarvis; Wen Liu; Shunke Ding; Ruixin Qu; Zhanghan Li; Cheng Ye; Wenhai Chu (Chemical Engineering Journal, 2024)

Superwettable calcium ion exchanged carboxymethyl cellulose powder with self-gelation, tissue adhesion and bioabsorption for effective hemorrhage control - Kaitao Yao; Shuyang Li; Xuzhou Zheng; Qian Zhang; Jinhui Liu; Cheng Liang; Ke Duan; Junwu Ye; Yiran Yin; Xingtao Chen (Chemical Engineering Journal, 2024)

Maintaining the concentration equilibrium of proton and hydroxide ions by construction of bis(2-aminoethyl)amine-based inner helmholtz plane toward long-life zinc metal anodes - Zhijian Wang; Zuyang Hu; Minghui Ye; Jiachi Chen; Yifa Chen; Zhipeng Wen; Yufei Zhang; Yongchao Tang; Xiaoqing Liu; Cheng Chao Li (Chemical Engineering Journal, 2024)

Establishment and characterization of DPC-X4: a novel mixed-type ampullary cancer cell line - Changpeng Chai; Huan Tang; Jianfeng Yi; Lu Li; Cheng Yu; Yuanhui Su; Long Miao; Zhenzhen Ye; Zhengfeng Wang; Wei Luo; Jinjing Hu; Hui Zhang; et al. (Human Cell, 2024)

Spatial-temporal variation of soil organic matter decomposition potential in China - Qi Chen; Zeyan Zhou; Sulin Cai; Meiqi Lv; Yinghui Yang; Yunchao Luo; Han Jiang; Run Liu; Tingting Cao; Bei Yao; Yunru Chen; Qiang Li; et al. (Soil and Tillage Research, 2024)

Environmental damages, cumulative exergy demand, and economic assessment of Panus giganteus farming with the application of solar technology - Hanting Cheng; Xiaohui Zhou; Yang Yang; Lin Xu; Ye Ding; Tingliang Yan; Qinfen Li (Science of The Total Environment, 2024)

A study on the mechanism of the impact of phenthoate exposure on Prorocentrum lima - Si-Wei Wu; Cai-Qin Cheng; Yi-Tong Huang; Jin-Zhou Tan; Song-Liang Li; Jia-Xin Yang; Xue-Ling Huang; Dan Huang; Li-Gong Zou; Wei-Dong Yang; Hong-Ye Li; Da-Wei Li (Journal of Hazardous Materials, 2024)

Green N1 additive modified perovskite precursor enables effective manufacturing of large-area solar cell modules with high efficiency and stability - Yue Zang; Yibo Tu; Chuanjia Jiao; Wangnan Li; Peng Zhou; Jiahao Cheng; Gaoyuan Yang; Tianxiang Shao; Jingchuan Ye; Guodong Li; Liang Chu; Shaojian Lu; et al. (Chemical Engineering Journal, 2024)

The role of oxide supports in constructing plasma-treated gold nanocatalysts for visible light photocatalytic oxidation of CO - Bin Zhu; Chong-Hua Zhong; Bang-You Jia; Tie Li; Jing-Lin Liu; Ye-Cheng Li; Yi-Min Zhu (Chemical Engineering Journal, 2024)

Application of adaptive laboratory evolution for Yarrowia lipolytica: A comprehensive review - Cheng Chen; Ya-Wen Li; Xin-Yu Chen; Yue-Tong Wang; Chao Ye; Tian-Qiong Shi (Bioresource Technology, 2024)

Historical trends and pollution assessment of heavy metals in core sediments from the Jiangsu offshore area, China - Li He; Shenghui Jiang; Xuhui Chen; Haiyan Cheng; Peng Ye; Lu Chen; Yuan Liu; Yanjun Yin; Xing Leng (Regional Studies in Marine Science, 2023)

Harmonization of semi-objective ANP with explained CRITIC for quantitative evaluation of fire hazard risks for flame-retardant materials - Bin Zou; Xin Wang; Jiajun Li; Zhenfeng Cheng; Guotao Ye; Wenhao Yang; Liangyuan Qi; Pengfei Jia; Fukai Chu; Zetao Xiao; Lei Song; Zhou Gui; et al. (Process Safety and Environmental Protection, 2023)

Limonoids from the roots of Melia azedarach and their anti-inflammatory activity - Min Song; Hui-Juan Luo; Zi-Wei Li; Ling Qiu; Yu-Xin Zhao; Cheng-Wei He; Xiao-Qi Zhang; Wen-Cai Ye; Li-Gen Lin; Qing-Wen Zhang (Phytochemistry, 2023)

Urban overall and visible greenness and diabetes among older adults in China - Kejia Hu; Zuhui Zhang; Yuanyuan Li; Shiyi Wang; Tingting Ye; Jinglu Song; Yunquan Zhang; Jing Wei; Jian Cheng; Yujie Shen; Jiahao Pan; Jingqiao Fu; et al. (Landscape and Urban Planning, 2023)

Joint effects of prenatal exposure to air pollution and pregnancy-related anxiety on birth weight: A prospective birth cohort study in Ma’anshan, China - Zhen-Hua Li; Yi-Cheng Mao; Yang Li; Sun Zhang; Hui-Yu Hu; Zhe-Ye Liu; Xue-Jie Liu; Jia-Wen Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Research, 2023)

STAT6 promoting oxalate crystal deposition-induced renal fibrosis by mediating macrophage-to-myofibroblast transition via inhibiting fatty acid oxidation - Tianhui Yuan; Yuqi Xia; Shengyu Pan; Bojun Li; Zehua Ye; Xinzhou Yan; Weimin Hu; Lei Li; Baofeng Song; Weimin Yu; Haoyong Li; Ting Rao; et al. (Inflammation Research, 2023)

Dietary nano-selenium improves health of liver and intestine of grass carp Ctenopharyngodon idella after overwintering - Limin Ye; Sha Liu; Xiaotian Zhang; Chi Wang; Pengju Li; Cheng Zhang; Hong Ji; Haibo Yu (Animal Feed Science and Technology, 2023)

Relationship of individual and mixed urinary metals exposure with liver function in the China National Human Biomonitoring (CNHBM) of Zhejiang Province - Ping Cheng; Yi Tao; Jinfeng Hu; Hongxin Wang; Ruifang Zhao; Shenghua Mei; Yin Yang; Fugen Ye; Zhijian Chen; Hao Ding; Mingluan Xing; Peiwei Xu; et al. (Chemosphere, 2023)

Genome architecture and tetrasomic inheritance of autotetraploid potato - Zhigui Bao; Canhui Li; Guangcun Li; Pei Wang; Zhen Peng; Lin Cheng; Hongbo Li; Zhiyang Zhang; Yuying Li; Wu Huang; Mingwang Ye; Daofeng Dong; et al. (Molecular Plant, 2023)

Tailoring pore structures in poly(propylene-co-1-butene) membranes: Unlocking versatility for advanced applications - Xian Zhang; Cheng-Ye Zhu; Wangbei Cao; Zhao-Yu Ma; Hao-Nan Li; Hong-Qing Liang; Chuan-Jie Fang; Xiao-Jun Huang; Zhi-Kang Xu (Chemical Engineering Journal, 2023)

NIR light-induced functionalized MXene as a dynamic-crosslinker for reinforced polyurethane composites with shape memory and self-healing - Qunyang Li; Hui He; Xun Ye; Fangrong Guan; Yuxuan Ai; Yue Shen; Cheng Zhang (Chemical Engineering Journal, 2023)

The modification of meteorological factors on the relationship between air pollution and periodontal diseases: an exploration based on different interaction strategies - Kai Huang; Lin-Fei Feng; Zhe-Ye Liu; Zhen-Hua Li; Yi-Cheng Mao; Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Ying-Qing Li; Jie Wang; Wen-Jie Yu; Xin Cheng; et al. (Environmental Geochemistry and Health, 2023)

Spatial distribution and influencing factors of China’s household biogas: evidence from provincial-level data - Zhenghao Liang; Chaojie Lan; Xin Jin; Shoupeng Li; Jinwen Cai; Shuyun Yang; Guangqing Hou; Wenxiao Cheng; Xujie Shao; Ruihong Jia; Jingang Ye; Dairen Shi; et al. (Environmental Science and Pollution Research, 2023)

PpeERF115 regulates peach fruit ripening by increasing polyamine turnover through up-regulation of genes involved in polyamine synthesis and catabolism - Xin Cheng; Zhenguo Cui; Yabo Jiang; Yang Chen; Bin Tan; Jun Cheng; Langlang Zhang; Xia Ye; Xiaobei Wang; Haipeng Zhang; Xiaodong Lian; Jidong Li; et al. (Postharvest Biology and Technology, 2023)

Increased ascorbic acid synthesis by overexpression of AcGGP3 ameliorates copper toxicity in kiwifruit - Xiaoying Liu; Chang Cheng; Yan Min; Xiaodong Xie; Abu Naim Md. Muzahid; Haiyan Lv; Hua Tian; Congxiao Zhang; Can Ye; Shifeng Cao; Peng Chen; Caihong Zhong; et al. (Journal of Hazardous Materials, 2023)

Peroxymonosulfate activation by sulfur doped CoFe2O4 rod for arsanilic acid removal: Performance and arsenic enrichment - Hanxuan Zeng; Bufan Yang; Wenfang Shi; Keqi Huang; Cheng Ye; Xiaoyan Ma; Zhijun Wang; Fei Huang; Xueyan Li; Jing Deng (Journal of Environmental Chemical Engineering, 2023)

Exploring HONO formation and its role in driving secondary pollutants formation during winter in the North China Plain - Shaobin Zhang; Guo Li; Nan Ma; Yao He; Shaowen Zhu; Xihao Pan; Wenlin Dong; Yanyan Zhang; Qingwei Luo; Jeannine Ditas; Uwe Kuhn; Yuxuan Zhang; et al. (Journal of Environmental Sciences, 2023)

Corn straw core/cellulose nanofibers composite for food packaging: Improved mechanical, bacteria blocking, ultraviolet and water vapor barrier properties - Zhimao Li; Jie Guan; Chunxia Yan; Nannan Chen; Can Wang; Tong Liu; Fangyue Cheng; Qing Guo; Xiaozhi Zhang; Xinming Ye; Yanhua Liu; Ziqiang Shao (Food Hydrocolloids, 2023)

A spheropolyhedral-based discrete element lattice Boltzmann method for simulation of non-spherical adhesive particulate flow - Ye-Cheng Qian; Rong-Rong Cai; Li-Zhi Zhang (Computer Physics Communications, 2023)

Electro-adsorption and reduction of Uranium(VI) by Fe3O4@COFs electrode with enhanced removal performance - Sen Yang; Zhouyi Ye; Xiaoya Cheng; Yuchun Wang; Zitong Luan; Wenjun Li; Baowei Hu (Chemical Engineering Journal, 2023)

Low air pressure self-sustaining combustion performances of 3D direct writing Al/CuO film - Yuxuan Zhou; Yueting Wang; Zehua Zhang; Fuwei Li; Jian Cheng; Yinghua Ye; Jianbing Xu; Ruiqi Shen (Chemical Engineering Journal, 2023)

Association of urinary heavy metal combined exposure with periodontitis among US adults from NHANES 2011–2014 - Zhen-Hua Li; Jiong Li; Yi-Cheng Mao; Jia-Wen Zhao; Hui-Yu Hu; Sun Zhang; Zhe-Ye Liu; Xue-Jie Liu; Kai Huang; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Science and Pollution Research, 2023)

The overlooked role of UV185 induced high-energy excited states in the dephosphorization of organophosphorus pesticide by VUV/persulfate - Yudan Liu; Jingke Wu; Nanchunxiao Cheng; Pengfei Gan; Yunyi Li; Wen Liu; Jiangyu Ye; Meiping Tong; Jialiang Liang (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Temporal expansion of the nighttime light images of SDGSAT-1 satellite in illuminating ground object extraction by joint observation of NPP-VIIRS and sentinel-2A images - Bo Yu; Fang Chen; Cheng Ye; Ziwen Li; Ying Dong; Ning Wang; Lei Wang (Remote Sensing of Environment, 2023)

Seasonal dynamics of coastal pollution migration in open waters with intensive marine ranching - Zhixin Cheng; Guoqiang Hong; Qingbo Li; Shangheng Liu; Shuang Wang; Ye Ma (Marine Environmental Research, 2023)

H2O2 activation and contaminants removal in heterogeneous Fenton-like systems - Ning Li; Xu He; Jingya Ye; Haoxi Dai; Wenchao Peng; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Shaobin Wang (Journal of Hazardous Materials, 2023)

High-efficient adsorption for versatile adsorbates by elastic reduced graphene oxide/Fe3O4 magnetic aerogels mediated by carbon nanotubes - Alei Dang; Xin liu; Yujia Wang; Yuhui Liu; Tao Cheng; Amir Zada; Fei Ye; Weibin Deng; Yiting Sun; Tingkai Zhao; Tiehu Li (Journal of Hazardous Materials, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Enhancing the combustion and propulsion performance of Al/CuO via introducing AlH3 as fuel substitute - Keer Ouyang; Jian Cheng; Zehua Zhang; Fuwei Li; Yinghua Ye; Ruiqi Shen (Fuel, 2023)

Microwave controlled ignition and combustion characteristics of ADN-based ionic liquid propellant with fast response and environmental friendliness - Jian Cheng; Jinle Cao; Fuwei Li; Zehua Zhang; Jianbing Xu; Keer Ouyang; Carole Rossi; Yinghua Ye; Ruiqi Shen (Chemical Engineering Journal, 2023)

A novel electrochemical aptasensor based on eco-friendly synthesized titanium dioxide nanosheets and polyethyleneimine grafted reduced graphene oxide for ultrasensitive and selective detection of ciprofloxacin - Yangguang Zhu; Xiufen Li; Mengfan Wu; Mingjiao Shi; Qichen Tian; Li Fu; Hsu-Sheng Tsai; Wan-Feng Xie; Guosong Lai; Gang Wang; Nan Jiang; Chen Ye; et al. (Analytica Chimica Acta, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Acer truncatum leaves reduce lipid accumulation and improve liver and intestine health of grass carp (Ctenopharyngodon idella) fed with high-fat diet - Limin Ye; Xiaotian Zhang; Chi Wang; Sha Liu; Pengju Li; Cheng Zhang; Qinfeng Gao; Hong Ji; Haibo Yu (Aquaculture, 2023)

Influence and mechanism of water matrices on H2O2-based Fenton-like oxidation processes: A review - Xiaoshuang Cheng; Lan Liang; Jingya Ye; Ning Li; Beibei Yan; Guanyi Chen (Science of The Total Environment, 2023)

Estimate provincial-level effectiveness of the arable land requisition-compensation balance policy in mainland China in the last 20 years - Chenyu Liu; Changqing Song; Sijing Ye; Feng Cheng; Leina Zhang; Chao Li (Land Use Policy, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Improving oxidation removal of toluene in plasma coupling perovskite catalysts system by constructing Au sites on a La0.5Ce0.5CoO3-δ - Bin Zhu; Qi-Wei Li; Ye-Cheng Li; Ya-Qiang Xia; Jing-Lin Liu; A-Min Zhou; Xiao-Min Zhang (Chemical Engineering Journal, 2023)

Propineb induced notochord deformity, craniofacial malformation, and osteoporosis in zebrafish through dysregulated reactive oxygen species generation - Wei Yuan; Ying Hu; Chen Lu; Jun Zhang; Ye Liu; Xinran Li; Kun Jia; Yong Huang; Zekun Li; Xiaomei Chen; Fei Wang; Xiaokun Yi; et al. (Aquatic Toxicology, 2023)

Involvement of Abnormal p-α-syn Accumulation and TLR2-Mediated Inflammation of Schwann Cells in Enteric Autonomic Nerve Dysfunction of Parkinson’s Disease: an Animal Model Study - Wenwen Jiang; Yue Cheng; Ye Wang; Jing Wu; Zhe Rong; Li Sun; Yan Zhou; Kezhong Zhang (Molecular Neurobiology, 2023)

Identification of Immune-Linked Hub Genes and Diagnostic Model Construction in Schizophrenia - Kun Lian; Zonglin Shen; Runxu Yang; Jing Ye; Binli Shang; Lei Dong; Hongfang Li; Jiabing Wu; Yuqi Cheng; Xiufeng Xu (Journal of Molecular Neuroscience, 2023)
Schizophrenia (SCZ) is a prevalent, severe, and persistent mental disorder with an unknown etiology. Growing evidence indicates that immunological dysfunction is vital in the development of SCZ. Our study aims to uncover potential immune-linked hub genes and immune infiltration characteristics of SCZ, as well as to develop a diagnostic model based on immune-linked central genes. GSE38484 and GSE54913 chip expression data for patients with SCZ and healthy controls were retrieved. Weighted gene co-expression network analysis (WGCNA) was performed to identify major module genes and critical immune-linked genes. Functional enrichment analysis was conducted to elucidate the involvement of key genes in the immunological response to SCZ, along with the examination of their protein interactions. Moreover, 202 peripheral blood samples were examined using the single-sample gene set enrichment analysis (ssGSEA) method to detect distinct immune cell types. Hub immune-linked genes in SCZ were identified using the minimal absolute contraction and selection operator analysis. Receptor profiles of central immune-linked genes were analyzed to distinguish the two groups. Finally, the association between immune-linked hub genes and various types of immune cells was assessed. Our findings revealed ten immune cell types and nine key genes involved in SCZ, including effector memory CD4+ T cells, activated CD8+ T cells, mast cells, naive CD8+ T cells, PBMC, type 17 helper cells (Th17), central memory CD8+ T cells, CD56 bright NK cells, memory B cells, and regulatory T cells. Diagnostic models constructed using LASSO regression exhibited an average area under the curve (AUC) of 0.866. Our results indicate immunological dysfunction as a factor in the development of SCZ. ASGR2 , ADRM1 , AHANK , S100A8 , FUCA1 , AKNA , GATA3 , AHCYL2 , and PTRH2 are the key regulatory genes of immune cells, highlighting their potential as novel therapeutic targets for SCZ.

Neurotoxicity of microplastics: a CiteSpace-based review and emerging trends study - Zeyan Ye; Tingyu Mai; Yuqian Cheng; Xiashuang Zhang; Zhe Liu; Zhiyong Zhang; You Li (Environmental Monitoring and Assessment, 2023)
Microplastics, as a currently emerging pollutant, are gaining increasing attention from researchers in various fields. The purpose of this study is to summarize research development on microplastics in the field of neurotoxicity using bibliometric tools and visualization methods and to identify current research hotspots. The Web of Science Core Collection (WoSCC) was searched under the topics of “microplastics” and “neurotoxicity.” A total of 33 published articles were obtained by exclusion and analyzed using CiteSpace (V6.1.R2). It was found that microplastic neurotoxicity research is currently on the rise, with the most research results being published in China, the most collaboration occurring between Italy and other countries, and the least collaboration occurring between authors. The focus and hotspots of future research on the neurotoxicity of microplastics may revolve around “accumulation” and “integrated biomarker response.” These findings demonstrate the trends and frontiers in the field of microplastic neurotoxicity research and provide valuable information for subsequent research directions and potential collaborations.

Alkylamides from Zanthoxylum armatum DC. and their neuroprotective activity - Qian-Nv Ye; Cheng-Bo Wang; Tian Chai; Jun Wang; Xian-Hua Meng; Xiao-Feng Shi; Jun-Li Yang (Phytochemistry, 2023)

Application of the global stability index method to shelf-life prediction and physiochemical characteristics analysis of enteral feeding formula during storage - Hong Yang; Li Li Xu; Ling Hou; Tong Cheng Xu; Shu Hong Ye (Journal of Food Engineering, 2023)

Corrigendum to “Aggravated multi-source air pollution exposure caused by open fires in China” [J. Clean. Prod. 394 (2023) 136402] - Xiaoyang Li; Tianhai Cheng; Hao Zhu; Xiaotong Ye (Journal of Cleaner Production, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Saltwater incursion regulates N2O emission pathways and potential nitrification and denitrification in intertidal wetland - Yinghui Jiang; Guoyu Yin; Ye Li; Lijun Hou; Min Liu; Cheng Chen; Dongsheng Zheng; Han Wu; Dengzhou Gao; Yanling Zheng; Ping Han (Biology and Fertility of Soils, 2023)

Revisiting China's domestic greenhouse gas emission from wastewater treatment: A quantitative process life-cycle assessment - Dengting Guo; Bing Li; Wei Yu; Jing-Cheng Han; Yang Zhou; Zhilong Ye; Xiaofeng Wu; Brent Young; Yuefei Huang (Science of The Total Environment, 2023)

Complete genome sequence and pathogenicity analysis of a highly pathogenic FAdV-4 strain - Kaili Wang; Cheng Liu; Xusheng Du; Ye Ma; Lele Chen; Shenliang Cao; Jianbiao Lu; Yubao Li; Zhenshu Si (Research in Veterinary Science, 2023)

Effects of sucrose degradation product furfural on cyanidin-3-O-glucoside: Mechanism of action, stability, and identification of products in sugar solutions - Jiaxin Wang; Zhen Cheng; Ningxuan Gao; Ye Zhang; Mingshuang Wang; Guangyu Ren; Baoge Song; Qi Liang; Yiwen Bao; Hui Tan; Wei Chen; Bin Li; et al. (Food Research International, 2023)

Recent development of sustainable self-healable electronic skin applications, a review with insight - Jean-Sébastien Benas; Fang-Cheng Liang; Manikandan Venkatesan; Zhen-Li Yan; Wei-Cheng Chen; Su-Ting Han; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2023)

Superhydrophobic, stretchable kirigami pencil-on-paper multifunctional device platform - Ye Xue; Zihan Wang; Ankan Dutta; Xue Chen; Peng Gao; Runze Li; Jiayi Yan; Guangyu Niu; Ya Wang; Shuaijie Du; Huanyu Cheng; Li Yang (Chemical Engineering Journal, 2023)

Improving Lignin Metabolism, Lodging Resistance, and Yield of Rapeseed (Brassica napus L.) by Applying Straw-Fermented Fertilizer - Yue Hu; Hafiz Hassan Javed; Yong-Li Du; Qi-Wen Liao; Wen Ye; Jing Zhou; Xiao Peng; Muhammad Arslan; Ali Raza; Yong-Cheng Wu (Journal of Soil Science and Plant Nutrition, 2023)

Aristolocholic acid I promotes renal tubular epithelial fibrosis by upregulating matrix metalloproteinase-9 expression via activating the C3a/C3aR axis of macrophages - Qi Zhang; Jing Ye; Zhaofeng Zhang; Yongkang Hu; Xian Wang; Wenjuan Jiang; Xinlong Guo; Langqun Chen; Siyu Cheng; Jian Li; Liang Zhang (Toxicology Letters, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

PpIBH1-1 limits internode elongation of peach shoot in a dose-dependent manner - Mengmeng Zhang; Beibei Feng; Yun Chen; Mingxi Geng; Ming Li; Xianbo Zheng; Haipeng Zhang; Langlang Zhang; Bin Tan; Xia Ye; Wei Wang; Jidong Li; et al. (Plant Science, 2023)

A combined method for human health risk area identification of heavy metals in urban environments - Yan Li; Zi Ye; Ye Yu; Ye Li; Jiang Jiang; Liangjie Wang; Genmei Wang; Huanchao Zhang; Ning Li; Xuefeng Xie; Xinyu Cheng; Ke Liu; et al. (Journal of Hazardous Materials, 2023)

Synthesis and biological evaluation of esculetin derivatives as potential anti-HBV agents - Zhen Ye; Tong-Shi-Yao Zhao; Shan-Bin Li; Xian-Li Zhou; Qin Luo; Jiang-Ke Qin; Cheng-Qin Liang; Ping Wang; Guang-Bo Ge (Medicinal Chemistry Research, 2023)

Peracetic acid activation via the synergic effect of Co and Fe in CoFe-LDH for efficient degradation of pharmaceuticals in hospital wastewater - Zhi-Hui Xie; Chuan-Shu He; Yong-Li He; Shu-Run Yang; Si-Ying Yu; Zhaokun Xiong; Ye Du; Yang Liu; Zhi-Cheng Pan; Gang Yao; Bo Lai (Water Research, 2023)

RETRACTED: Determining the spatial non-stationarity underlying social and natural environment in thyroid cancer in China - Xiyu Zhang; Yongqiang Lai; Xiaodan Bai; Bing Wu; Wenjing Xiang; Chenxi Zhang; Guihong Geng; Wenqing Miao; Qi Xia; Qunhong Wu; Huiying Yang; Yanjie Wang; et al. (Science of The Total Environment, 2023)

Responses of microbial community to geochemical parameters on vertical depth in bioheap system of low-grade copper sulfide - Xiu-Tong Li; Zhong-Sheng Huang; Ye Huang; Zhen Jiang; Zong-Lin Liang; Hua-Qun Yin; Guang-Ji Zhang; Yan Jia; Ye Deng; Shuang-Jiang Liu; Cheng-Ying Jiang (Science of The Total Environment, 2023)

Transcriptome, proteome and metabolome analysis provide insights on fat deposition and meat quality in pig - Taiyong Yu; Xuekai Tian; Dong Li; Yulin He; Peiyu Yang; Ye Cheng; Xin Zhao; Jingchun Sun; Gongshe Yang (Food Research International, 2023)

Microstructural evolution during acid induced gelation of cow, goat, and sheep milk probed by time-resolved (ultra)-small angle neutron scattering - Zhi Yang; Lirong Cheng; Liliana de Campo; Elliot Paul Gilbert; Rainer Mittelbach; Lan Luo; Aiqian Ye; Siqi Li; Yacine Hemar (Food Hydrocolloids, 2023)

Acid-tailored self-assembled perylene diimide supramolecular for visible-light-driven activation of peroxymonosulfate towards efficient degradation of iohexol - Qiuyi Ji; Kexun Du; Jiandong Zhu; Xiaoqian Ye; Hongjian Li; Xinying Cheng; Yazi Liu; Zhe Xu; Gancheng Zuo; Shiyin Li; Shaogui Yang; Limin Zhang; et al. (Chemical Engineering Journal, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Whole-genome sequencing reveals putative underlying mechanisms of biocontrol capability of IBFCBF-5 - Chen Luo; Ai-rong Shen; Ye-song Ren; Yang Zhai; Yi Cheng; Jianping Xu; Lin Wei; Ji-lie Li; Liang-bin Zeng (Acta Physiologiae Plantarum, 2023)

Impact of satellite AOD data on top-down estimation of biomass burning particulate matter emission - Xiaotong Ye; Tianhai Cheng; Xiaoyang Li; Hao Zhu (Science of The Total Environment, 2023)

Nanoplastics promote arsenic-induced ROS accumulation, mitochondrial damage and disturbances in neurotransmitter metabolism of zebrafish (Danio rerio) - Cheng Zhang; Yanyao Li; Haibo Yu; Limin Ye; Tian Li; Xiaotian Zhang; Chi Wang; Pengju Li; Hong Ji; Qinfeng Gao; Shuanglin Dong (Science of The Total Environment, 2023)

Application of MXene-based materials in Fenton-like systems for organic wastewater treatment: A review - Chuanbin Wang; Jingya Ye; Lan Liang; Xiaoqiang Cui; Lingchao Kong; Ning Li; Zhanjun Cheng; Wenchao Peng; Beibei Yan; Guanyi Chen (Science of The Total Environment, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

Aggravated multi-source air pollution exposure caused by open fires in China - Xiaoyang Li; Tianhai Cheng; Hao Zhu; Xiaotong Ye (Journal of Cleaner Production, 2023)

Simultaneous determination of dissolved organic nitrogen, nitrite, nitrate and ammonia using size exclusion chromatography coupled with nitrogen detector - Wen-Xiang Ji; Ye-Chao Tian; Min-Hui Cai; Bi-Cun Jiang; Shi Cheng; Yan Li; Qing Zhou; Bo-Qiang Li; Bai-Yang Chen; Xing Zheng; Wen-Tao Li; Ai-Min Li (Journal of Environmental Sciences, 2023)

A predictive model on deoxynivalenol in harvested wheat in China: Revealing the impact of the environment and agronomic practicing - Sen Li; Ningjing Liu; Di Cai; Cheng Liu; Jin Ye; Bingjie Li; Yu Wu; Li Li; Songxue Wang; H.J. van der Fels-Klerx (Food Chemistry, 2023)

Metabolomics and molecular simulation reveal the responding mechanism of anammox consortia to perfluorooctanoic acid by regulating metabolic network - Dong-Qi Huang; Ye Wang; Zi-Yue Li; Bao-Cheng Huang; Min Yang; Nian-Si Fan; Ren-Cun Jin (Chemical Engineering Journal, 2023)

Overexpressing SIRT6 can Attenuate the Injury of Intracerebral Hemorrhage by Down-Regulating NF-kB - Jing Cheng; Yan-Qin Fan; Wen-Fei Zhang; Guo Zhang; Kuo Zeng; Zhang Ye; Dan Zhao; Li-Quan Wu; Zhi-Biao Chen (NeuroMolecular Medicine, 2023)

Shaking table test and numerical simulation of free field in sand-sawdust mixed soil - Xueju Li; Danguang Pan; Ying Huang; Ye Cheng; Xiangqiu Fu (Soil Dynamics and Earthquake Engineering, 2023)

Kojicone C, new anti-inflammatory polyketide from insect-associated fungus Aspergillus versicolor - Tian-Xiao Li; Chi Zhang; Feng-Cheng Shi; Ye Ye; Jia-Le Huang; Lei Wu; Chun-Ping Xu (Phytochemistry Letters, 2023)

Nitrogen-doped porous biochar for selective adsorption of toluene under humid conditions - Tangying Cheng; Ye Bian; Jinjin Li; Xiuwei Ma; Linjun Yang; Lei Zhou; Hao Wu (Fuel, 2023)

The impact of heating rate on the decomposition kinetics and product distribution of algal waste pyrolysis with in-situ weight measurement - Muxuan Li; Ye Shui Zhang; Shuo Cheng; Boyu Qu; Aimin Li; Fandongkun Meng; Guozhao Ji (Chemical Engineering Journal, 2023)

Promising energy-storage applications by flotation of graphite ores: A review - Ye Chen; Shilong Li; Shiru Lin; Mingzhe Chen; Cheng Tang; Xinghui Liu (Chemical Engineering Journal, 2023)

Graphite intercalation compounds (GICs) based multi-functional interface layer toward highly reversible Zn metal anodes - Shunzhang You; Dao-Sheng Liu; Minghui Ye; Yufei Zhang; Yongchao Tang; Xiaoqing Liu; Cheng Chao Li (Chemical Engineering Journal, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

The effect of climate and vegetation variation on monthly sediment load in a karst watershed - Si Cheng; Xingxiu Yu; Zhenwei Li; Xianli Xu; Huayi Gao; Zongda Ye (Journal of Cleaner Production, 2023)

Confined Fe single atomic sites on (100) plane of anatase TiO2 nanofibers boost white LED driven Fenton-like norfloxacin degradation - Zhilin Ji; Rongsheng Cai; Wanneng Ye; Ping Lu; Chung-Li Dong; Yu-Cheng Huang; Xilin She; Denys S. Butenko; Yiming Liu; Yukun Zhu; Dongjiang Yang (Journal of Cleaner Production, 2023)

Enhancing hydrodeoxygenation-isomerization of FAME over M-SAPO-11 in one-step process: Effect of in-situ isomorphic substitution of transition metals and synergy of PtxSny alloy - Xingyong Li; Qiyuan Fan; Yankun Wu; Xin Lin; Sihan Ma; Shuirong Li; Yueyuan Ye; Dechao Wang; Jun Cheng; Zhifeng Zheng; Jianchun Jiang (Chemical Engineering Journal, 2023)

Intermittent electric field stimulated reduction-oxidation coupled process for enhanced azo dye biodegradation - Ye Yuan; Wanxin Yin; Yutong Huang; Anqi Feng; Tianming Chen; Liang Qiao; Haoyi Cheng; Wenzong Liu; Zhaoxia Li; Cheng Ding; Fan Chen; Aijie Wang (Chemical Engineering Journal, 2023)

Coaxial electrospinning fabrication of core-shell energetic fibers and in-situ integration with SCB exhibiting superior non-contact ignition - Zehua Zhang; Jian Cheng; Yueting Wang; Fuwei Li; Yun Shen; Cheng-ai Wang; Jianbing Xu; Ruiqi Shen; Yinghua Ye (Chemical Engineering Journal, 2023)

Doping of Al/CuO with microwave absorbing Ti3C2 MXene for improved ignition and combustion performance - Jian Cheng; Zehua Zhang; Yueting Wang; Fuwei Li; Jinle Cao; Michael Gozin; Yinghua Ye; Ruiqi Shen (Chemical Engineering Journal, 2023)

SnoRNP is essential for thermospermine-mediated development in Arabidopsis thaliana - Xilong Li; Zongyun Yan; Meiling Zhang; Jiayin Wang; Peiyong Xin; Shujing Cheng; Liquan Kou; Xiaoting Zhang; Songlin Wu; Jinfang Chu; Chengqi Yi; Keqiong Ye; et al. (Science China Life Sciences, 2023)

Brevibacillus daliensis sp. nov., Isolated From Soil in Machangqing Nature Reserve - Shi-Qiang Ye; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; Zhu-Feng Shi; et al. (Current Microbiology, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Toxic Effect of Combined Exposure of Microplastics and Copper on Goldfish (Carassius auratus): Insight from Oxidative Stress, Inflammation, Apoptosis and Autophagy in Hepatopancreas and Intestine - Cheng Zhang; Limin Ye; Chi Wang; Xiaofan Xiong; Yanyao Li; Pengju Li; Xiaotian Zhang; Haibo Yu (Bulletin of Environmental Contamination and Toxicology, 2022)

Comparing Catch Efficiency of Crayfish (Procambarus clarkii) Traps with Different Entrance Numbers - Zhaohai Cheng; Margaret H. Folkins; Liuyi Huang; Ye Li (Journal of Marine Science and Engineering, 2022)
Traps with various designs have been developed for improving catch efficiency. Traditionally, traps with two or three entrances have been used in recreational crayfish (Procambarus clarkii) fisheries in China. More recently, traps with more than three entrances have been used in fisheries; however, it is unclear whether increasing the number of entrances on a trap increases crayfish capture efficiency. In this research, we evaluated and compared the capture efficiency of crayfish with traps varying in numbers of entrances (2–7). We assessed the catch per unit effort (CPUE) of crayfish in traps through 10 fishing trials. Our results suggested that CPUE did not differ significantly (p = 0.070) among the tested traps; however, CPUE by weight did vary significantly (p = 0.029) among the traps. The tested six-entrance traps caught more crayfish by weight than the five-entrance traps (p = 0.019). The results also revealed that the entrance number did not significantly (p = 0.29) affect the size of crayfish captured. The results are of practical significance for stakeholders to choose traps with efficient designs, and they are important for understanding and improving the catch efficiency of traps.

Developmental Exposure to Bisphenol a Degrades Auditory Cortical Processing in Rats - Binliang Tang; Kailin Li; Yuan Cheng; Guimin Zhang; Pengying An; Yutian Sun; Yue Fang; Hui Liu; Yang Shen; Yifan Zhang; Ye Shan; Étienne de Villers-Sidani; et al. (Neuroscience Bulletin, 2022)

Associations of metal profiles in blood with thyroiditis: a cross-sectional study - Yaosheng Luo; Huixian Zeng; Yanshi Ye; Genfeng Yu; Cheng Song; Siyang Liu; Xingying Chen; Yuqi Jiang; Hualin Duan; Yue Li; Shengqing He; Zhi Chen; et al. (Environmental Science and Pollution Research, 2022)
Autoimmune thyroiditis (AIT) is increasingly common, and serological markers include thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb). To determine if selected metals influence thyroiditis antibody positivity, this cross-sectional study investigated associations between metals and thyroiditis antibody status. Healthy individuals ( n = 1104) completed a questionnaire and underwent checkups of anthropometric parameters, thyroid function status, and levels of seven metals in blood (magnesium, iron, calcium, copper, zinc, manganese, and lead). Associated profiles of glyco- and lipid metabolism were also established. Logistic regression and restricted cubic spline (RCS) regression analysis were applied to adjudge associations between metals and TPOAb and TgAb status. It was found that, after adjusting for likely cofounding factors, participants with antibody positivity had significantly lower serum concentrations of magnesium and iron. When serum magnesium levels were analyzed in quartiles, the odds ratios of quartile 4 were 0.329–fold (95% confidence interval (CI): 0.167–0647) and 0.259-fold (95% CI 0.177–0.574) that of quartile 1 regarding TPOAb and TgAb positivity ( P = 0.004, 0.003). After adjustment, the RCS analysis detected nonlinear associations between iron and TPOAb and TgAb positivity ( P < 0.01, both). In stratified analyses, these associations regarding magnesium and iron remained for women of reproductive age, but not for postmenopausal women and men. We conclude that lower serum levels of magnesium and iron are associated with incremental positivity of thyroiditis antibodies and may be among the most important metals contributing to AIT in women of reproductive age.

The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Cheng-He Sun; Rodolphe Elie Gozlan; Ting Wu; Dan Xue; Ye-Ling Lao; Jian-Feng Yu; Xiao-Shu Zeng; Sha Li; Emilie A. Hardouin; Demetra Andreou; Qun Zhang (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical, and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources and for the setup of efficient protected area networks for the conservation of marine species. In this study, we used extensive sampling of Sebastiscus marmoratus , a commercially important inshore rockfish with high site fidelity, to characterize their population genetic structure along the China–Japan coast and to determine the effect of past geological and current biological–physical barriers on the current genetic footprint. A 461-bp fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographical locations. A total of 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise fixation index ( F ST ) and analysis of molecular variance (AMOVA) revealed significant genetic differentiation among populations. The Bayesian skyline plots and neutrality statistics showed a sudden expansion of the S. marmoratus population around the Pleistocene. The Beibu Gulf group had the lowest mean number of pairwise differences, the lowest significant genetic differentiation, and the lowest haplotype and nucleotide diversity, and should be prioritized for protection in the future. Ocean currents, seascape discontinuity, geographical distance, and ecological characteristics may play an important role in shaping the contemporary phylogeographical patterns and population structures of S. marmoratus .

Long-term changes in zooplankton in the Changjiang estuary from the 1960s to 2020 - Ping Du; Wen-Jian Ye; Bang-Ping Deng; Ming Mao; Yuan-Li Zhu; Fang-Ping Cheng; Zhi-Bing Jiang; Lu Shou; Quan-Zhen Chen (Frontiers in Marine Science, 2022)
The Changjiang estuary (CJE) is a large estuary that is affected by multiple anthropogenic stressors and climate change. The long-term trend of zooplankton in the CJE is an important indicator of the ecological response to stressors. We applied the Mann–Kendall trend analysis and Pettitt test to detect the trend and breakpoints of the biomass of the large mesozooplankton (LMZ; 505–20 000 μm) in four seasons, abundance of main LMZ taxa in summer from the 1960s to 2020, and abundance of dominant species in summer from 2000 to 2020 in the CJE. Results showed that LMZ biomass increased significantly during spring and summer, and the breakpoints both occurred in the 1980s. After the breakpoint, the mean biomass increased from 142.88 to 429.42 mg/m 3 in spring and from 296.28 to 723.92 mg/m 3 in summer. After 2000, the abundance of Copepoda in summer increased by more than 10 times compared to the 1960s. Under the conditions of warming and increased dinoflagellate abundance in the CJE, the abundance of the warm-water and omnivorous small calanoid copepod Paracalanus aculeatus increased significantly. Meanwhile, the significant decrease in the abundance of the temperate brackish species Labidocera euchaeta was probably mainly related to warming. The rapid changes in LMZ biomass during the late 1980s and mid-1990s is probably the result of a combination of enhanced bottom–up support, reduced top–down pressure, and promotion of temperature. This study provides scientific evidence and insights into the adaptive management of the Changjiang Basin.

Synthesis and in vitro biological evaluation of novel dendrocandin analogue as potential anti-tumor agent - Jing-Yun Yan; Hao-Nan Yang; Ning Yang; Yin-Rong Xie; Xiu-Li Sun; Ye-Wei Huang; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Natural Product Research, 2022)

Cohnella mopanensis sp. nov., a new Gram-negative bacterium isolated from soil in Xinping Mountain National Forest Park - Jing Tang; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Shi-Qiang Ye; Cheng Ling; Meng-Yu Zhang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; et al. (Archives of Microbiology, 2022)

Sevoflurane inhibits the malignant phenotypes of glioma through regulating miR-146b-5p/NFIB axis - Haili Wang; Guofang Cheng; Lili Quan; Haibo Qu; Ailing Yang; Jiangge Ye; Yuanbo Feng; Xiaofang Li; Xiaoli Shi; Hua Pan (Metabolic Brain Disease, 2022)

Prediction of the sea buckthorn AQP gene structure and its spatiotemporal expression pattern under drought stress - Dan Zhang; Nanxiang Yang; Jiawei Dong; Cheng Wang; Qiangfeng Li; Rong Wang; Zhipeng Feng; Dejuan Xie; Guisheng Ye; Yuhua Ma (Journal of Plant Biochemistry and Biotechnology, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Multiple indeterminate domain (IDD)–DELLA1 complexes participate in gibberellin feedback regulation in peach - Yajun Jiang; Jiajia Chen; Xianbo Zheng; Bin Tan; Xia Ye; Wei Wang; Langlang Zhang; Jidong Li; Zhiqian Li; Jun Cheng; Jiancan Feng (Plant Molecular Biology, 2022)

Indoor air pollution from solid fuel on children pneumonia in low- and middle-income countries: a systematic review and meta-analysis - Tianming Chen; Chao Zou; Yang Yuan; Jingjing Pan; Baoping Zhang; Liang Qiao; Yanping Li; Jia-yan Qian; Qingyuan Guo; Ye Yuan; Cheng Ding (Environmental Science and Pollution Research, 2022)

Load transfer laws of tensile anchors in rock masses with weak interlayers based on a shear-slipping updating model - Yan Wang; Xin Xiang; Chang-dong Li; Guo-qiang Zhu; Cheng-bin Song; Jin-ye Xian; Jia-jun Zhang (Journal of Mountain Science, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

GIS-based spatial prediction of landslide using road factors and random forest for Sichuan-Tibet Highway - Cheng-ming Ye; Rui-long Wei; Yong-gang Ge; Yao Li; José Marcato Junior; Jonathan Li (Journal of Mountain Science, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Clinical Value of 3D-Printed Navigation Technology Combined with Neuroendoscopy for Intracerebral Hemorrhage - Yuqian Li; Hongyu Cheng; Zhenzhu Li; Haikang Zhao; Jiancai Wang; Peng Wang; Tongxin Jin; Guiyong Zheng; Haoxiang Ye; Shaopeng Li; Jun Zhang (Translational Stroke Research, 2021)

Longitudinal virological changes and underlying pathogenesis in hospitalized COVID-19 patients in Guangzhou, China - Zhengtu Li; Yinhu Li; Ruilin Sun; Shaoqiang Li; Lingdan Chen; Yangqing Zhan; Mingzhou Xie; Jiasheng Yang; Yanqun Wang; Airu Zhu; Guoping Gu; Le Yu; et al. (Science China Life Sciences, 2021)

Dammarane-type saponins from Gynostemma pentaphyllum and their cytotoxicities - Wei-Ye Cui; Yulian Jin; Hui Liu; Ma-Li Zu; Xin-Fang Zhai; Ce Yang; Yu-Long Gu; Yong Cheng; Xiang-Lan Piao (Natural Product Research, 2021)

Correlations between Dual-Pathway White Matter Alterations and Language Impairment in Patients with Aphasia: A Systematic Review and Meta-analysis - Jie Zhang; Shuchang Zhong; Liang Zhou; Yamei Yu; Xufei Tan; Min Wu; Peng Sun; Wei Zhang; Juebao Li; Ruidong Cheng; Yanfei Wu; Yanmei Yu; et al. (Neuropsychology Review, 2021)

Modulation of the 5-HT 3 A receptor current by desacylbaldrinal - Li-Xia Wang; Hu-Lan Chen; Hong-Ling Yan; Fei Tang; Hai Zhang; Hong-Xiang Li; Qiang Ye; Cheng Peng; Yu-Zhu Tan (Natural Product Research, 2021)

Discovery of N-phenyl-1-(phenylsulfonamido)cyclopropane-1-carboxamide analogs as NLRP3 inflammasome inhibitors - Wanwan Li; Zhongqiang Cao; Junjie Cheng; Feiyu Chen; Shuai Li; Yiwei Huang; Long Tai Zheng; Na Ye (Medicinal Chemistry Research, 2021)

Sliding speed calculation of the Wenchuan earthquake fault using the Doppler effect - Qi-Cheng Li; Shu-Geng He; Min Ye (Applied Geophysics, 2021)

Design of supercontinuum laser hyperspectral light detection and ranging (LiDAR) (SCLaHS LiDAR) - Guoqing Zhou; Xiang Zhou; Youjian Song; Donghui Xie; Long Wang; Guangjian Yan; Minglie Hu; Bowen Liu; Weidong Shang; Chenghu Gong; Cheng Wang; Huaguo Huang; et al. (International Journal of Remote Sensing, 2021)

Orbital-scale Asian summer monsoon variations: Paradox and exploration - Hai Cheng; Haiwei Zhang; Yanjun Cai; Zhengguo Shi; Liang Yi; Chenglong Deng; Qingzhen Hao; Youbing Peng; Ashish Sinha; Hanying Li; Jingyao Zhao; Ye Tian; et al. (Science China Earth Sciences, 2021)

Molecular Identification and Phylogenetic Analysis of the Traditional Chinese Medicinal Plant Kochia scoparia Using ITS2 Barcoding - Jingan Chen; Silu Li; Wenru Wu; Jingyi Xie; Xuemei Cheng; Zixin Ye; Xiaoqing Yin; Yong Liu; Zunnan Huang (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Polyamine oxidase (PAO)–mediated polyamine catabolism plays potential roles in peach (Prunus persica L.) fruit development and ripening - Wei Wang; Xianbo Zheng; Shihao Liu; Bin Tan; Jun Cheng; Xia Ye; Jidong Li; Jiancan Feng (Tree Genetics & Genomes, 2021)

Construction and characterization of UAA-controlled recombinant Zika virus by genetic code expansion - Rong-Rong Zhang; Qing Ye; Xiao-Feng Li; Yong-Qiang Deng; Yan-Peng Xu; Xing-Yao Huang; Qing Xia; Cheng-Feng Qin (Science China Life Sciences, 2021)

Permeability Evolution of Two-Dimensional Fracture Networks During Shear Under Constant Normal Stiffness Boundary Conditions - Bo Li; Ruyi Bao; Ye Wang; Richeng Liu; Cheng Zhao (Rock Mechanics and Rock Engineering, 2021)

High-throughput sequencing reveals the molecular mechanisms determining the stay-green characteristic in soybeans - Cheng Wang; Le Gao; Run Zhi Li; Ye Wang; Yang Ying Liu; Xin Zhang; Hao Xie (Journal of Biosciences, 2020)

The effect of blastomere loss during frozen embryo transfer on the transcriptome of offspring’s umbilical cord blood - Yan-Ting Wu; Ze-Han Dong; Cheng Li; Dai-Zhan Zhou; Jun-Yu Zhang; Yan Wu; Jing-Jing Xu; Yu Wang; Xiao-Qun Ye; Jian-Zhong Sheng; Li Wang; He-Feng Huang (Molecular Biology Reports, 2020)

The anti-inflammatory drug dimethyl itaconate protects against colitis-associated colorectal cancer - Qian Wang; Xin Ling Li; Yan Mei; Jia-Chong Ye; Wei Fan; Guang-Hui Cheng; Mu-Sheng Zeng; Guo-Kai Feng (Journal of Molecular Medicine, 2020)

Mixture of Pb, Zn and Cu on root permeability and radial oxygen loss in the mangrove Bruguiera gymnorrhiza - Hao Cheng; You-Shao Wang; Chang-Da Li; Zhi-Hong Ye; Shafi Muhammad; Mei-Lin Wu; Fun-Lin Sun (Ecotoxicology, 2020)

Impact of Climate Change on Wintering Ground of Japanese Anchovy (Engraulis japonicus) Using Marine Geospatial Statistics - Shuhao Liu; Yang Liu; Irene D. Alabia; Yongjun Tian; Zhenjiang Ye; Haiqing Yu; Jianchao Li; Jiahua Cheng (Frontiers in Marine Science, 2020)

Genetic diversity of Prorocentrum donghaiense population during bloom in the East China Sea revealed by microsatellite - Hong-jia Huang; Chu-qiao Gan; Shao-wen Xiao; Cheng Zou; Srinivasan Balamurugan; Hong-ye Li; Jie-sheng Liu; Wei-dong Yang (Journal of Applied Phycology, 2020)

Improved production of GTKO/hCD55/hCD59 triple-gene-modified Diannan miniature pigs for xenotransplantation by recloning - Heng Zhao; Yuying Li; Thanapa Wiriyahdamrong; Zaimei Yuan; Yubo Qing; Honghui Li; Kaixiang Xu; Jianxiong Guo; Baoyu Jia; Xuezeng Zhang; Wenmin Cheng; Yanhua Su; et al. (Transgenic Research, 2020)

Naturally Occurring Antibodies to Tau Exists in Human Blood and Are Not Changed in Alzheimer’s Disease - Zhong-Yuan Yu; Wei-Wei Li; Hai-Mei Yang; Noralyn B. Mañucat-Tan; Jun Wang; Ye-Ran Wang; Bin-Lu Sun; Zi-Cheng Hu; Li-Li Zhang; Liang Tan; Juan Deng; Yu-Hui Liu (Neurotoxicity Research, 2020)

A new aryldihydronaphthalene-type lignan and other metabolites with potential anti-​inflammatory activities from Corispermum mongolicum Iljin - Yi Zhou; Mei Jin; Chunshi Jin; Chao Ye; Jiaming Wang; Jinfeng Sun; Cheng-Xi Wei; Wei Zhou; Gao Li (Natural Product Research, 2020)

Chitin synthase is involved in vegetative growth, asexual reproduction and pathogenesis of Phytophthora capsici and Phytophthora sojae - Wei Cheng; Menglan Lin; Min Qiu; Liang Kong; Yuanpeng Xu; Yaning Li; Yan Wang; Wenwu Ye; Suomeng Dong; Shuilin He; Yuanchao Wang (Environmental Microbiology, 2019)
Summary Chitin is a structural and functional component of the fungal cell wall and also serves as a pathogen‐associated molecular pattern (PAMP) that triggers the innate immune responses of host plants. However, no or very little chitin is found in the fungus‐like oomycetes. In Phytophthora spp., the presence of chitin has not been demonstrated so far, although putative chitin synthase (CHS) genes, which encode the enzymes that synthesize chitin, are present in their genomes. Here, we revealed that chitin is present in the zoospores and released sporangia of Phytophthora , and this is most consistent with the transcriptional pattern of PcCHS in Phytophthora capsici and PsCHS1 in Phytophthora sojae . Disruption of the CHS genes indicated that PcCHS and PsCHS1 , but not PsCHS2 (which exhibited very weak transcription), have similar functions involved in mycelial growth, sporangial production, zoospore release and the pathogenesis of P. capsici and P. sojae . We also suggest that chitin in the zoospores of P. capsici can act as a PAMP that is recognized by the chitin receptors AtLYK5 or AtCERK1 of Arabidopsis . These results provide new insights into the biological significance of chitin and CHSs in Phytophthora and help with the identification of potential targets for disease control.

A new glycoprotein SPG-8700 isolated from sweet potato with potential anti-cancer activity against colon cancer - Cheng Tian; Meimei Wang; Shanshan Liu; Hang Ma; Kai He; Deqi Zhou; Yanlin Li; Xiaoli Ye; Xuegang Li (Natural Product Research, 2019)

Phosphate adsorption from wastewater using ZnAl-LDO-loaded modified banana straw biochar - Yan-Hong Jiang; An-Yu Li; Hua Deng; Cheng-Hui Ye; Yi Li (Environmental Science and Pollution Research, 2019)

Genome-wide identification of Ziziphus jujuba TCP transcription factors and their expression in response to infection with jujube witches’ broom phytoplasma - Peng Chen; Jidong Li; Xia Ye; Bin Tan; Xianbo Zheng; Jun Cheng; Wei Wang; Huiyu Wang; Liyuan Gu; Jiancan Feng (Acta Physiologiae Plantarum, 2019)

Waterlogging tolerance of Bidens pilosa translates to increased competitiveness compared to native Bidens biternata - Maofeng Yue; Hao Shen; Weihua Li; Jinfeng Chen; Wanhui Ye; Xingshan Tian; Aiguo Yin; Shuiming Cheng (Plant and Soil, 2019)

Socially controlled male‐to‐female sex reversal in the protogynous orange‐spotted grouper, Epinephelus coioides - Jiaxing Chen; Ling Xiao; Cheng Peng; Zhifeng Ye; Dengdong Wang; Yuqing Yang; Haifa Zhang; Mi Zhao; Shuisheng Li; Haoran Lin; Yong Zhang (Journal of Fish Biology, 2019)
Socially controlled sex change in teleosts is a dramatic example of adaptive reproductive plasticity. In many cases, the occurrence of sex change is triggered by a change in the social context, such as the disappearance of the dominant individual. The orange‐spotted grouper Epinephelus coioides is a typical protogynous hermaphrodite fish that changes sex from female to male and remains male throughout its life span. In this study, male‐to‐female sex reversal in male Epinephelus coioides was successfully induced by social isolation. The body length and mass, gonadal change, serum sex steroid hormone levels and sex‐related gene expression patterns during the process of socially controlled male‐to‐female sex reversal in E. coioides were systematically examined. This report investigates the physiological mechanisms of the socially controlled male‐to‐female sex reversal process in a protogynous hermaphrodite grouper species. The results enable us to study the physiological control of sex change, not only from female to male, but also from male to female.

Correction to: Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Functional analysis of the UL24 protein of suid herpesvirus 1 - Chao Ye; Jing Chen; Xuefei Cheng; Shasha Zhou; Shan Jiang; Jingjing Xu; Hao Zheng; Wu Tong; Guoxin Li; Guangzhi Tong (Virus Genes, 2019)

Correlation between microbes and colorectal cancer: tumor apoptosis is induced by sitosterols through promoting gut microbiota to produce short-chain fatty acids - Hang Ma; Yang Yu; Meimei Wang; Zhaoxing Li; Heshan Xu; Cheng Tian; Jian Zhang; Xiaoli Ye; Xuegang Li (Apoptosis, 2019)

The influence of porcine epidemic diarrhea virus on pig small intestine mucosal epithelial cell function - Xing-Ye Wang; Tai-Qiang Zhao; De-Peng Xu; Xue Zhang; Cheng-Jie Ji; De-Li Zhang (Archives of Virology, 2019)

Development and characterization of 27 SNP markers in the Mauremys mutica transcriptome - Zhang Xin-Cheng; Zhao Jian; Li Wei; Liu Yi-Hui; Wei Cheng-Qing; Wang Ya-Kun; Ye Zhao-Yang; Zhu Xin-Ping (Conservation Genetics Resources, 2018)

The relative importance of space compared to topography increases from rare to common tree species across latitude - Yue‐Hua Hu; Daniel J. Johnson; Xiang‐Cheng Mi; Xu‐Gao Wang; Wan‐Hui Ye; Yi‐De Li; Ju‐Yu Lian; Min Cao (Journal of Biogeography, 2018)
Aim Understanding how spatial distributions of rare and common species are associated with environmental and spatial processes is essential to understanding community assembly. We addressed the following questions: (a) does the relative importance of space and topography vary from rare to common tree species? (b) Are the contributions of topography and space equal? (c) Are the variances explained by topography or space correlated with elevational ranges (ER) at the local scale? (d) Does cell‐size influence those postulated associations? Location China and the Americas. Major taxa studied Tree species. Methods We partitioned the variation in species richness and composition of rare and common tree species by topography and space across a range of extents and grain sizes in eight communities. We calculated contribution ratio ( CR ) between space and topography to quantify their relative importance. We employed Kendall's rank correlation to determine the relation between CR and commonness. Mixed effect models were used to identify the influence of cell‐size on the results. Results The majority of CR values were positively related to increasing commonness, especially for composition. The explained variances by space were always higher than that by topography regardless of commonness. At local scale, variances explained by space or topography were not correlated with ER. Main conclusions Our results indicate that the relative importance of space compared to topography increases from rare to common species across forests. We suggest that future studies of community assembly need to account for both space and topography to adequately describe differences in rare and common species assembly mechanisms at range of spatial extents and grain sizes.

Repaglinide-irbesartan drug interaction: effects of SLCO1B1 polymorphism on repaglinide pharmacokinetics and pharmacodynamics in Chinese population - Qi Pei; Jun-Yan Liu; Ji-Ye Yin; Guo-Ping Yang; Shi-Kun Liu; Yi Zheng; Pan Xie; Cheng-Xian Guo; Mi Luo; Hong-Hao Zhou; Xi Li; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2018)

Dopamine D4 Receptor Gene Associated with the Frontal-Striatal-Cerebellar Loop in Children with ADHD: A Resting-State fMRI Study - Andan Qian; Xin Wang; Huiru Liu; Jiejie Tao; Jiejie Zhou; Qiong Ye; Jiance Li; Chuang Yang; Jingliang Cheng; Ke Zhao; Meihao Wang (Neuroscience Bulletin, 2018)

Early middle Holocene climate oscillations recorded in the Beihuqiao Core, Yuhang, Zhejiang Province, China - Wei Ye; Qu Chen; Lidong Zhu; Fengquan Li; Tianyang Wang; Longjuan Cheng; Yunxia Zhang (Journal of Paleolimnology, 2018)

Effect of dietary astaxanthin on the growth performance, non-specific immunity, and antioxidant capacity of pufferfish (Takifugu obscurus) under high temperature stress - Chang-Hong Cheng; Zhi-Xun Guo; Chao-Xia Ye; An-Li Wang (Fish Physiology and Biochemistry, 2018)

Zoledronate dysregulates fatty acid metabolism in renal tubular epithelial cells to induce nephrotoxicity - Lili Cheng; Mengmeng Ge; Zhou Lan; Zhilong Ma; Wenna Chi; Wenhua Kuang; Kun Sun; Xinbin Zhao; Ye Liu; Yaqian Feng; Yuedong Huang; Maoguo Luo; et al. (Archives of Toxicology, 2018)

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans - Mengbi Yang; Jianqing Ruan; Hong Gao; Na Li; Jiang Ma; Junyi Xue; Yang Ye; Peter Pi-Cheng Fu; Jiyao Wang; Ge Lin (Archives of Toxicology, 2017)

Development of a stable Japanese encephalitis virus replicon cell line for antiviral screening - Qiu-Yan Zhang; Xiao-Dan Li; Si-Qing Liu; Cheng-Lin Deng; Bo Zhang; Han-Qing Ye (Archives of Virology, 2017)

Modern greenhouse culture of juvenile soft-shelled turtle, Pelodiscus sinensis - Jing Zhang; Fen Wang; Ye-Lin Jiang; Guan-Jun Hou; Yun-Sheng Cheng; Hong-Lian Chen; Xiang Li (Aquaculture International, 2017)

Association of Toll-like receptor 3 gene polymorphism with the severity of enterovirus 71 infection in Chinese children - Hongfang He; Shihai Liu; Pei-pei Liu; Qiu-bo Li; Yu-xia Tan; Ya Guo; Fei Li; Yuan-yuan Wang; Ye-dan Liu; Cheng-qing Yang; Zong-bo Chen (Archives of Virology, 2017)

AntarcticaLC2000: The new Antarctic land cover database for the year 2000 - FengMing Hui; Jing Kang; Yan Liu; Xiao Cheng; Peng Gong; Fang Wang; Zhan Li; YuFang Ye; ZiQi Guo (Science China Earth Sciences, 2017)

Prognostic value of human papillomavirus 16/18 genotyping in low-grade cervical lesions preceded by mildly abnormal cytology - Jing Ye; Bei Cheng; Yi-fan Cheng; Ye-li Yao; Xing Xie; Wei-guo Lu; Xiao-dong Cheng (Journal of Zhejiang University-SCIENCE B, 2017)

Human papillomavirus (HPV) E6/E7 mRNA detection in cervical exfoliated cells: a potential triage for HPV-positive women - Ye-li Yao; Qi-fang Tian; Bei Cheng; Yi-fan Cheng; Jing Ye; Wei-guo Lu (Journal of Zhejiang University-SCIENCE B, 2017)

Distributed mixed-integer fuzzy hierarchical programming for municipal solid waste management. Part II: scheme analysis and mechanism revelation. - Guanhui Cheng; Guohe Huang; Cong Dong; Ye Xu; Jiapei Chen; Xiujuan Chen; Kailong Li (Environmental Science and Pollution Research, 2017)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

Preparation and In Vitro/In Vivo Evaluation of Puerarin Solid Self-Microemulsifying Drug Delivery System by Spherical Crystallization Technique - Gang Cheng; Rongfeng Hu; Lei Ye; Bin Wang; Yun Gui; Song Gao; Xiaoxiang Li; Jihui Tang (AAPS PharmSciTech, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

A disputed evidence on obesity: comparison of the effects of Rcan2−/− and Rps6kb1−/− mutations on growth and body weight in C57BL/6J mice - Jing Zhao; Shi-wei Li; Qian-qian Gong; Ling-cui Ding; Ye-cheng Jin; Jian Zhang; Jian-gang Gao; Xiao-yang Sun (Journal of Zhejiang University-SCIENCE B, 2016)

Se Enhances MLCK Activation by Regulating Selenoprotein T (SelT) in the Gastric Smooth Muscle of Rats - Jia-ping Li; Jing-xuan Zhou; Qi Wang; Gao-qin Gu; Shi-jin Yang; Cheng-ye Li; Chang-wei Qiu; Gan-zhen Deng; Meng-yao Guo (Biological Trace Element Research, 2016)

Fine mapping of the dialytic gene that controls multicellular trichome formation and stamen development in tomato - Jiang Chang; Ting Yu; Shenghua Gao; Cheng Xiong; Qingmin Xie; Hanxia Li; Zhibiao Ye; Changxian Yang (Theoretical and Applied Genetics, 2016)

The Regulatory Roles of ncRNA Rli60 in Adaptability of Listeria monocytogenes to Environmental Stress and Biofilm Formation - Ye-long Peng; Qing-ling Meng; Jun Qiao; Kun Xie; Cheng Chen; Tian-li Liu; Zheng-xiang Hu; Yu Ma; Xue-peng Cai; Chuang-fu Chen (Current Microbiology, 2016)

MRP functional activity and character in the dinoflagellate Prorocentrum lima - Dao-yi Hou; Jin-jin Liang; Cheng Zou; Hong-ye Li; Jie-sheng Liu; Wei-dong Yang (Journal of Applied Phycology, 2016)

GiT-based structural geologic feature analysis of the southern segment of Longmenshan fault zone for earthquake evidence - Cheng-ming Ye; Peng Cui; Saied Pirasteh; Jonathan Li; Qingkai Meng; Xiao-jia Bi; Jian-qiang Zhang (Journal of Mountain Science, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Factors Associated with Thrombolysis Outcome in Ischemic Stroke Patients with Atrial Fibrillation - Qiuyun Zhao; Xiaobo Li; Wanli Dong; Min Ye; Yongjun Cao; Meijuan Zhang; Qiantao Cheng; Junshan Zhou; Guofang Chen; Ming Yu; Shanshan Hong; Xiue Wei; et al. (Neuroscience Bulletin, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Editing of the Luteinizing Hormone Gene to Sterilize Channel Catfish, Ictalurus punctatus, Using a Modified Zinc Finger Nuclease Technology with Electroporation - Zhenkui Qin; Yun Li; Baofeng Su; Qi Cheng; Zhi Ye; Dayan A. Perera; Michael Fobes; Mei Shang; Rex A. Dunham (Marine Biotechnology, 2016)

Identification and Evaluation of Reliable Reference Genes in the Medicinal Fungus Shiraia bambusicola - Liang Song; Tong Li; Li Fan; Xiao-Ye Shen; Cheng-Lin Hou (Current Microbiology, 2016)

In vivo activity of vancomycin combined with colistin against multidrug-resistant strains of Acinetobacter baumannii in a Galleria mellonella model - Haifei Yang; Na Lv; Lifen Hu; Yanyan Liu; Jun Cheng; Ying Ye; Jiabin Li (Infectious Diseases, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Concomitant coronary and renal revascularization improves left ventricular hypertrophy more than coronary stenting alone in patients with ischemic heart and renal disease - Hao-jian Dong; Cheng Huang; De-mou Luo; Jing-guang Ye; Jun-qing Yang; Guang Li; Jian-fang Luo; Ying-ling Zhou (Journal of Zhejiang University-SCIENCE B, 2016)

Clinical and molecular genetic analysis of a Chinese family with congenital X-linked adrenal hypoplasia caused by novel mutation 1268delA in the DAX-1 gene - Zhe Zhang; Ye Feng; Dan Ye; Cheng-jiang Li; Feng-qin Dong; Ying Tong (Journal of Zhejiang University-SCIENCE B, 2015)

Identification, characterization and functional analysis of anti-apoptotic protein BCL-2-like gene from pufferfish, Takifugu obscurus, responding to bacterial challenge - Chang-Hong Cheng; Fang-Fang Yang; Shao-An Liao; Yu-Tao Miao; Chao-Xia Ye; An-Li Wang; Jin-Chang Liu; Li-Wei Liu (Fish Physiology and Biochemistry, 2015)

Amanita subpallidorosea, a new lethal fungus from China - Hai-Jiao Li; Jian-Wei Xie; Shuo Zhang; Ya-Juan Zhou; Pei-Bin Ma; Jing Zhou; Cheng-Ye Sun (Mycological Progress, 2015)

Genetic Association Between APP, ADAM10 Gene Polymorphism, and Sporadic Alzheimer’s Disease in the Chinese Population - Fan Zeng; Cheng Shen; Yu-Hui Liu; Jing Li; Jie Zhu; Ye-Ran Wang; Jia-Chuan Yan; Chang-Yue Gao; Hua-Dong Zhou; Juan Deng; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Effect of acute ammonia exposure on expression of GH/IGF axis genes GHR1, GHR2 and IGF-1 in pufferfish (Takifugu obscurus) - Chang-Hong Cheng; Fang-Fang Yang; Shao-An Liao; Yu-Tao Miao; Chao-Xia Ye; An-Li Wang (Fish Physiology and Biochemistry, 2015)

Testing the mutant selection window hypothesis in vitro and in vivo with Staphylococcus aureus exposed to fosfomycin - Q. Mei; Y. Ye; Y.-L. Zhu; J. Cheng; X. Chang; Y.-Y. Liu; H.-R. Li; J.-B. Li (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

A new continuous cell line from Blaps rhynchoptera Fairmaire (Coleoptera: Tenebrionidae) - Xin Zhang; Ying Feng; Wei-Feng Ding; Xian Li; Cheng-Ye Wang (In Vitro Cellular & Developmental Biology - Animal, 2015)

A Highly Selective and Sensitive Probe for Cu2+ Based on Rhodamine-Pyridazine Conjugate and its Application - Peigang Ding; Shao Li; Linchao Yang; Junye Cheng; Zhenji Wang; Yufen Zhao; Yong Ye (Journal of Fluorescence, 2015)

Identification of a potential novel type of influenza virus in Bovine in China - Wen-Ming Jiang; Su-Chun Wang; Cheng Peng; Jian-Min Yu; Qing-Ye Zhuang; Guang-Yu Hou; Shuo Liu; Jin-Ping Li; Ji-Ming Chen (Virus Genes, 2014)

5-HT2A receptor-mediated excitation on cerebellar fastigial nucleus neurons and promotion of motor behaviors in rats - Chang-Zheng Zhang; Qian-Xing Zhuang; Ye-Cheng He; Guang-Ying Li; Jing-Ning Zhu; Jian-Jun Wang (Pflügers Archiv - European Journal of Physiology, 2014)

Synthesis of bufalin derivatives with inhibitory activity against prostate cancer cells - Xiao-Feng Yuan; Hai-Yan Tian; Juan Li; Lu Jin; Shu-Tai Jiang; Ken Wing-Keung Liu; Cheng Luo; David A. Middleton; Mikael Esmann; Wen-Cai Ye; Ren-Wang Jiang (Natural Product Research, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Activation of mammalian target of rapamycin contributes to pain nociception induced in rats by BmK I, a sodium channel-specific modulator - Feng Jiang; Li-Ming Hua; Yun-Lu Jiao; Pin Ye; Jin Fu; Zhi-Jun Cheng; Gang Ding; Yong-Hua Ji (Neuroscience Bulletin, 2014)

Synthesis and analgesic evaluation of a series of proline-typed spiro cyclic quaternary ammoniums - Songwen Lin; Na Wang; Shuo Zhao; Qi Sun; Weiwei Zhang; Jia Ye; Tieming Cheng; Runtao Li (Medicinal Chemistry Research, 2014)

Cidea controls lipid droplet fusion and lipid storage in brown and white adipose tissue - LiZhen Wu; LinKang Zhou; Cheng Chen; JingYi Gong; Li Xu; Jing Ye; De Li; Peng Li (Science China Life Sciences, 2014)

MicroRNA-98 induces an Alzheimer’s disease-like disturbance by targeting insulin-like growth factor 1 - Yi-Kui Hu; Xun Wang; Lian Li; Yan-Hua Du; Heng-Tai Ye; Cheng-Yan Li (Neuroscience Bulletin, 2013)

Structural features of GABAA receptor antagonists: pharmacophore modeling and 3D-QSAR studies - Wei Zhang; Shuang Xia; Jinjin Ye; Yun Tang; Zhong Li; Weiping Zhu; Jiagao Cheng (Medicinal Chemistry Research, 2013)

The complete S RNA and M RNA nucleotide sequences of a hippeastrum chlorotic ringspot virus (HCRV) isolate from Hymenocallis littoralis (Jacq.) Salisb in China - Ye Xu; Shi-gao Lou; Xiao-lin Li; Yuan-xian Zheng; Wen-cheng Wang; Ya-ting Liu (Archives of Virology, 2013)

Transcriptome profiling and digital gene expression analysis of Nile tilapia (Oreochromis niloticus) infected by Streptococcus agalactiae - Rui Zhang; Li-li Zhang; Xing Ye; Yuan-yuan Tian; Cheng-fei Sun; Mai-xin Lu; Jun-jie Bai (Molecular Biology Reports, 2013)

Association of IL-1 Receptor Antagonist Gene VNTR Polymorphism with Ischemic Stroke in the Chinese Uyghur Population - Yeqing Tong; Jinjun Han; Xuhua Guan; Zuxun Lu; Xiaoping Miao; Jianjun Ye; Shuang-yi Hou; Yanwei Zhang; Yijie Geng; Yang Li; Faxian Zhan; Jiafa Liu; et al. (Biochemical Genetics, 2013)

Establishment and characterization of a cell line developed from the neonate larvae of Papilio demoleus Linnaeus (Lepidoptera: Papilionidae) - Wei-Feng Ding; Ying Feng; Xin Zhang; Xian Li; Cheng-Ye Wang (In Vitro Cellular & Developmental Biology - Animal, 2013)

An improved Landsat Image Mosaic of Antarctica - FengMing Hui; Xiao Cheng; Yan Liu; YanMei Zhang; YuFang Ye; XianWei Wang; Zhan Li; Kun Wang; ZhiFei Zhan; JianHong Guo; HuaBing Huang; XiuHong Li; et al. (Science China Earth Sciences, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Anti-arthritic effects of crocin in interleukin-1β-treated articular chondrocytes and cartilage in a rabbit osteoarthritic model - Qianhai Ding; Huiming Zhong; Yiying Qi; Ye Cheng; Weijun Li; Shigui Yan; Xianghua Wang (Inflammation Research, 2013)

Endogenous signal peptides efficiently mediate the secretion of recombinant proteins in Pichia pastoris - Shuli Liang; Cheng Li; Yanrui Ye; Ying Lin (Biotechnology Letters, 2013)

Whole-body vibration and resistance exercise prevent long-term hindlimb unloading-induced bone loss: independent and interactive effects - Zhili Li; Cheng Tan; Yonghua Wu; Ye Ding; Huijuan Wang; Wenjuan Chen; Yu Zhu; Honglei Ma; Honghui Yang; Wenbin Liang; Shizhong Jiang; Desheng Wang; et al. (European Journal of Applied Physiology, 2012)

Effects of copper on growth, radial oxygen loss and root permeability of seedlings of the mangroves Bruguiera gymnorrhiza and Rhizophora stylosa - Hao Cheng; Nora Fung-Yee Tam; Youshao Wang; Shiyu Li; Guizhu Chen; Zhihong Ye (Plant and Soil, 2012)

Internal ribosome entry site mediates protein synthesis in yeast Pichia pastoris - Shuli Liang; Ying Lin; Cheng Li; Yanrui Ye (Biotechnology Letters, 2012)

Evaluation of High-Resolution Melting for Gene Mapping in Rice - Jinshan Li; Xuming Wang; Ruixian Dong; Yong Yang; Jie Zhou; Chulang Yu; Ye Cheng; Chengqi Yan; Jianping Chen (Plant Molecular Biology Reporter, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Artesunate inhibits growth and induces apoptosis in human osteosarcoma HOS cell line in vitro and in vivo - Qiang Xu; Zhao-xu Li; Hui-qin Peng; Zheng-wang Sun; Rui-lin Cheng; Zhao-ming Ye; Wei-xu Li (Journal of Zhejiang University-SCIENCE B, 2011)

Bufadienolide compounds sensitize human breast cancer cells to TRAIL-induced apoptosis via inhibition of STAT3/Mcl-1 pathway - Yinhui Dong; Shutao Yin; Jinghua Li; Cheng Jiang; Min Ye; Hongbo Hu (Apoptosis, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

China’s wetland change (1990–2000) determined by remote sensing - Peng Gong; ZhenGuo Niu; Xiao Cheng; KuiYi Zhao; DeMin Zhou; JianHong Guo; Lu Liang; XiaoFeng Wang; DanDan Li; HuaBing Huang; Yi Wang; Kun Wang; et al. (Science China Earth Sciences, 2010)

Structural basis for the action of xyloglucan endotransglycosylases/hydrolases: Insights from homology modeling - Qin Xu; Xia Ye; Li-Yan Li; Zong-Ming Cheng; Hong Guo (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Epidemiological study of human calicivirus infection in children with gastroenteritis in Lanzhou from 2001 to 2007 - Wei-xia Cheng; Xin-hua Ye; Xue-mei Yang; Yu-ning Li; Miao Jin; Yu Jin; Zhao-jun Duan (Archives of Virology, 2010)

Phenotypic and molecular characterization of two novel CTX-M enzymes carried by Klebsiella pneumoniae - Jun Cheng; Wei Gao; Jun Yin; Zhen Sun; Ying Ye; Yu-Feng Gao; Xu Li; Jia-Bin Li (Molecular Biology Reports, 2010)

A “GC-rich” method for mammalian gene expression: A dominant role of non-coding DNA GC content in regulation of mammalian gene expression - Qian Jia; HongTao Wu; XingJun Zhou; Jian Gao; Wei Zhao; JouDi Aziz; JingShuang Wei; Lihua Hou; Shuyin Wu; Ying Zhang; XiangFeng Dong; YanMin Huang; et al. (Science China Life Sciences, 2010)

Identification of the flavin-dependent monooxygenase-encoding YUCCA gene family in Populus trichocarpa and their expression in vegetative tissues and in response to hormone and environmental stresses - Xia Ye; Byung-guk Kang; Lori D. Osburn; Yi Li; Cheng Zong-Ming (Max) (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

A novel SHV-type β-lactamase variant (SHV-89) in clinical isolates in China - Jia-Bin Li; Jun Cheng; Qian Wang; Yan Chen; Ying Ye; Xue-Jun Zhang (Molecular Biology Reports, 2009)

Osteogenic differentiation of mesenchymal stem cells promoted by overexpression of connective tissue growth factor - Jin-jing Wang; Feng Ye; Li-jia Cheng; Yu-jun Shi; Ji Bao; Huai-qiang Sun; Wei Wang; Peng Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2009)

Morphology, ecology, and contaminant removal efficiency of eight wetland plants with differing root systems - Xiu-Yun Cheng; Wen-Yin Chen; Bin-He Gu; Xu-Cheng Liu; Fang Chen; Zhang-He Chen; Xian-Ye Zhou; Yu-Xiang Li; Hua Huang; Yun-Jin Chen (Hydrobiologia, 2009)

Characterization of a Novel AmpC-Type Plasmid-Mediated β-Lactamase from an Escherichia coli Strain Isolated in China - Qian Wang; Jun Cheng; Yan Chen; Ying Ye; Jia-Bin Li; Xue-Jun Zhang (Current Microbiology, 2008)

Localization of a novel gene for congenital nonsyndromic simple microphthalmia to chromosome 2q11-14 - Hui Li; Jia-Xin Wang; Cheng-Ye Wang; Ping Yu; Qiang Zhou; Yong-Gang Chen; Lu-Hang Zhao; Ya-Ping Zhang (Human Genetics, 2008)

Effect of lead on ERK activity and the protective function of bFGF in rat primary culture astroglia - Ying Zhang; Li-ping Ye; Biao Wang; Shi-cheng Cao; Li-guang Sun (Journal of Zhejiang University-SCIENCE B, 2007)

Application of cDNA array for studying the gene expression profile of mature appressoria of Magnaporthe grisea - Qing-chao Jin; Hai-tao Dong; You-liang Peng; Bao-shan Chen; Jing Shao; Ye Deng; Cheng-en Dai; Yong-qi Fang; Yi-chun Lou; You-zhi Li; De-bao Li (Journal of Zhejiang University-SCIENCE B, 2007)

Discussion on the forming factors of dog-tooth crystal and stone coral in Furong cave, Chongqing city, China - Qiao Chen; Kun-li Luo; Ke Hu; Ming-xing Dong; Cheng-li Ye; Qiang Liu (Carbonates and Evaporites, 2006)

Cloning and Characterization of a Second form of the Rice Adenine Phosphoribosyl Transferase Gene (OsAPT2) and its Association with TGMS - Chun-Jiang Zhou; Jun Li; Ji-Cheng Zou; Feng-Shan Liang; Chun-Jiang Ye; De-Min Jin; Man-Li Weng; Bin Wang (Plant Molecular Biology, 2006)

Minimizing phenol pollution in sugarcane stem apical meristem culture - Cheng-Mei Huang; Yang-Rui Li; Yan-Ping Ye (Sugar Tech, 2003)

Isolation and characterization of a human putative receptor protein kinase cDNA STYK1* - Xin Ye; Chaoneng Ji; Qingshan Huang; Chao Cheng; Rong Tang; Jian Xu; Li Zeng; Jianfeng Dai; Qihan Wu; Shaohua Gu; Yi Xie; Yumin Mao (Molecular Biology Reports, 2003)

Note: Isolation and Characterization of a Novel Human Putative Anemia-Related Gene Homologous to Mouse Sideroflexin - Xin Ye; Jian Xu; Chao Cheng; Gang Yin; Li Zeng; Chaoneng Ji; Shaohua Gu; Yi Xie; Yumin Mao (Biochemical Genetics, 2003)

Cloning, expression and characterization of a novel human VMP gene* - Chao Cheng; Jian Xu; Xin Ye; Jianfeng Dai; Qihan Wu; Li Zeng; Liu Wang; Wei Zhao; Chaoneng Ji; Shaohua Gu; Yi Xie; Yumin Mao (Molecular Biology Reports, 2002)

Inheritance and expression of the cry1Ab gene in Bt (Bacillus thuringiensis) transgenic rice - G. Wu; H. Cui; G. Ye; Y. Xia; R. Sardana; X. Cheng; Y. Li; I. Altosaar; Q. Shu (Theoretical and Applied Genetics, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)